Method for manufacturing magnetic substrate, and magnetic substrate
By using a resin composition containing a magnetic powder containing a specific alloy powder and a thermosetting resin on the surface of the magnetic layer, the conductor layer is directly formed by an electroplating method, which solves the problems of many processes, difficult control and complex component management in the prior art, and achieves the effects of simplifying the process, shortening time and improving smoothness.
Patent Information
- Application Number
- CN202380062075.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-02
- Filing Date
- 2023-08-16
- Publication Date
- 2025-04-04
AI Technical Summary
In the prior art, in order to form a conductor layer on the surface of the magnetic layer, a combination of electroless plating and electroplating is required. The number of steps is large, the control is difficult, and the composition management of the plating solution is complex.
By including a cured product of a resin composition containing a specific range of (A-1) alloy powder and a (B) thermosetting resin on the surface of the magnetic layer, the conductor layer is directly formed by an electroplating method, and the electroless plating step is omitted.
The manufacturing process of magnetic substrates is simplified, the number of processes is reduced, the preparation time is shortened, the complexity of the plating solution component management is reduced, and the smoothness of the conductor layer is improved.
Smart Images

Figure CN119769180A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for manufacturing a magnetic substrate and a magnetic substrate. Background Art
[0002] Substrates with inductors are often mounted on information terminals such as mobile phones and smartphones. In the past, independent inductor components were mounted on substrates such as circuit boards, but in recent years, a method has been proposed in which a coil is formed using a conductor layer of a substrate and an inductor is directly mounted on the substrate (Patent Document 1).
[0003] Prior art literature Patent Literature Patent Document 1: Japanese Patent Application Publication No. 2021 / 086856 Summary of the invention
[0004] Technical problem to be solved by the invention As a method of directly setting the inductor on the substrate, for example, there is a known method of using a cured product of a resin composition containing a magnetic material to form a magnetic layer in the hole of the substrate, and forming a conductor layer on the surface of the magnetic layer. The conductor layer is usually formed by a plating method. In the plating method, electroless plating can form a conductor layer on the surface of a non-conductive material, but on the other hand, it is usually difficult to thicken the conductor layer. On the other hand, electroplating generally cannot form a conductor layer on the surface of a non-conductive material based on the principle of using electric current, so it is impossible to form a conductor layer on the surface of a magnetic layer that is a non-conductive layer. Therefore, in the past, a thin conductor layer (seed layer) was usually formed on the surface of the magnetic layer by electroless plating, and a thick conductor layer was formed on the thin conductor layer by electroplating.
[0005] However, when electroless plating and electroplating are combined, the number of steps required to form a conductor layer is large. If the number of steps is large, there is a tendency that many control items for plating are required, and the time required to form a conductor layer is long. Furthermore, generally, strict component management is required for the plating solution as a chemical solution for electroless plating. Therefore, the time required for the component management of the plating solution is large, and the component management of the plating solution becomes complicated.
[0006] Therefore, it is necessary to develop a technology that can omit electroless plating and form a conductor layer on the surface of a magnetic layer by electroplating.
[0007] The present invention is proposed in view of the above-mentioned problems, and its purpose is to provide: a manufacturing method of a magnetic substrate including forming a conductor layer on the surface of a magnetic layer by electroplating; a magnetic substrate including a magnetic layer and a conductor layer formed on the surface of the magnetic layer by electroplating.
[0008] Means of solving technical problems The present inventors have conducted intensive research to solve the above-mentioned problems. As a result, the present inventors have found that a conductor layer can be formed by electroplating on the surface of a cured product of a resin composition comprising (A) magnetic powder containing an amount of (A-1) alloy powder in a specific range and (B) a thermosetting resin. Furthermore, the present inventors have obtained the following knowledge: by applying the above-mentioned cured product to a magnetic layer, the above-mentioned problems can be solved, thereby completing the present invention. That is, the present invention includes the following contents.
[0009] [1] A method for producing a magnetic substrate comprising a magnetic layer and a conductive layer formed on a surface of the magnetic layer, The manufacturing method includes a step (EP) of forming a conductor layer on the surface of the magnetic layer by electroplating. The magnetic layer includes a cured product of a resin composition including (A) magnetic powder and (B) a thermosetting resin, wherein the (A) magnetic powder includes 30% by mass or more of (A-1) alloy powder relative to 100% by mass of the (A) magnetic powder. [2] The method for producing a magnetic substrate according to [1], wherein before step (EP), the method comprises: a step of forming a resin composition layer (LF) comprising a resin composition, and A step (CU) of curing the resin composition layer to form a magnetic layer. [3] The method for producing a magnetic substrate according to [2], wherein the step of forming a conductor layer on the surface of the magnetic layer by a method other than electroplating is not included between step (CU) and step (EP). [4] The method for producing a magnetic substrate according to [2] or [3], wherein step (LF) includes forming a resin composition layer in the first holes of the substrate having the first holes formed therein. [5] The method for producing a magnetic substrate according to any one of [1] to [4], comprising, before step (EP), a step (HF) of forming a second hole in the magnetic layer. Step (EP) includes forming a conductor layer on the surface of the magnetic layer in the second hole by electroplating. [6] The method for producing a magnetic substrate according to any one of [1] to [5], wherein the amount of the (A) magnetic powder is 60% by mass or more relative to 100% by mass of the non-volatile components in the resin composition. [7] The method for producing a magnetic substrate according to any one of [1] to [6], wherein the relative magnetic permeability of the cured product at a measurement frequency of 20 MHz is 10 or more. [8] The method for producing a magnetic substrate according to any one of [1] to [7], wherein the (A-1) alloy powder comprises one or more selected from Fe-Ni alloy powder, Fe-Cr-Si alloy powder and Fe-Ni-Cr alloy powder. [9] A magnetic substrate comprising a magnetic layer having holes formed therein and a conductive layer formed in the holes, wherein the magnetic layer is in direct contact with the conductive layer and no plating catalyst is present at the interface between the magnetic layer and the conductive layer, and the magnetic layer comprises a cured product of a resin composition, wherein the resin composition comprises (A) a magnetic powder and (B) a thermosetting resin, and the (A) magnetic powder comprises 30% by mass or more of an (A-1) alloy powder relative to 100% by mass of the (A) magnetic powder.
[10] The magnetic substrate according to [9], wherein the conductor layer is formed of copper. Effects of the Invention
[0010] According to the present invention, there can be provided: a method for manufacturing a magnetic substrate including the step of forming a conductor layer on the surface of a magnetic layer by electroplating; and a magnetic substrate including a magnetic layer and a conductor layer formed on the surface of the magnetic layer by electroplating. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] Figure 1 It is a schematic cross-sectional view for explaining the process of the manufacturing method of the magnetic substrate involved in one example. Figure 2 It is a schematic cross-sectional view for explaining the process of the manufacturing method of the magnetic substrate involved in one example. Figure 3 It is a schematic cross-sectional view for explaining the process of the manufacturing method of the magnetic substrate involved in one example. Figure 4 It is a schematic cross-sectional view for explaining the process of the manufacturing method of the magnetic substrate involved in one example. Figure 5 It is a schematic cross-sectional view for explaining the process of the manufacturing method of the magnetic substrate involved in one example. Figure 6 It is a schematic cross-sectional view for explaining the process of the manufacturing method of the magnetic substrate involved in one example. Figure 7 It is a schematic cross-sectional view for explaining the process of the manufacturing method of the magnetic substrate involved in one example. Figure 8 It is a schematic cross-sectional view for explaining the process of the manufacturing method of the magnetic substrate involved in one example. Fig. 9 It is a schematic cross-sectional view for explaining the process of the manufacturing method of the magnetic substrate involved in one example. Fig.10It is a schematic cross-sectional view for explaining the process of the manufacturing method of the magnetic substrate involved in one example. Fig.11 It is a schematic cross-sectional view for explaining the process of the manufacturing method of the magnetic substrate involved in one example. Fig.12 1 is a schematic cross-sectional view of a magnetic substrate according to an example. DETAILED DESCRIPTION
[0012] Hereinafter, embodiments and examples of the present invention will be shown and described in detail. However, the present invention is not limited to the following embodiments and examples, and can be implemented with arbitrary modifications within the scope of the claims and their equivalents. In the following description, unless otherwise specified, the resin component of the resin composition means the component other than the inorganic particles such as the (A) magnetic powder in the non-volatile components of the resin composition.
[0012] [Overview of the method for producing a magnetic substrate] A manufacturing method according to one embodiment of the present invention is a manufacturing method for a magnetic substrate having a magnetic layer and a conductor layer formed on the surface of the magnetic layer. The magnetic layer comprises a cured product of a resin composition containing (A) magnetic powder and (B) a thermosetting resin. In addition, the (A) magnetic powder comprises an amount of (A-1) alloy powder in a specific range. On the surface of such a magnetic layer, a conductor layer can be formed by electroplating, so the formation of a conductor layer (seed layer) by electroless plating can be omitted. Therefore, the manufacturing method according to the present embodiment may include a step (EP) of forming a conductor layer on the surface of the magnetic layer by electroplating. The above-mentioned conductor layer formed on the surface of the magnetic layer by electroplating is sometimes referred to as an "electroplated layer" hereinafter.
[0014] Since the formation of the conductor layer (seed layer) using electroless plating can be omitted, the manufacturing method involved in this embodiment can reduce the number of processes and form the electroplated layer simply and in a short time. In addition, since electroless plating is not required, a chemical solution for electroless plating is not required. Therefore, the component management of the chemical solution is not required, so the manufacturing process of the magnetic substrate can be simplified. In this regard, if a chemical solution for electroless plating is used, depending on the type of (A-1) alloy powder, sometimes (A-1) alloy powder is dissolved in the chemical solution, and the complexity of the component management of the chemical solution increases, forming a contrast. Furthermore, even particles of materials that can be dissolved or deteriorated by the chemical solution can be used as (A-1) alloy powder, so the selection range of (A-1) alloy powder can be expanded. Moreover, the magnetic layer containing (A-1) alloy powder in this way can usually have excellent magnetic properties.
[0015] Generally, in electroplating, metal ions in the plating solution are reduced and precipitated on the surface of the cathode to be plated, thereby forming a conductor layer. In order to reduce the metal ions, it is necessary to apply an electric current, so it is common knowledge among those skilled in the art that the reduction of metal ions occurs only on the surface of the cathode formed by the conductor. For example, even if electroplating is performed, a conductor layer cannot be formed on the surface of a magnetic layer with a large volume resistivity.
[0016] In contrast, in the present embodiment, the magnetic layer of the (A) magnetic powder containing the (A-1) alloy powder in a specific range has a greater resistance than the conductor, and a plated layer as a conductor layer can be formed on the surface of the magnetic layer by electroplating. Even if the magnetic layer involved in the present embodiment has a volume resistance equivalent to that of a conventional magnetic layer, an electroplated layer can be formed on the surface of the magnetic layer involved in the present embodiment of the (A) magnetic powder containing the (A-1) alloy powder in a specific range by an electroplated layer. This phenomenon is unexpected to those skilled in the art.
[0017] Although the present invention is not bound by a specific theory, the inventors speculate as follows on the mechanism of forming the electroplated layer on the surface of the magnetic layer by electroplating. It is assumed that a wiring is connected to the magnetic layer for electroplating. Generally, the (A-1) alloy powder has conductivity, but all or most of the particles of the (A-1) alloy powder are generally insulated due to the resin component. Therefore, the magnetic layer generally has insulating properties. However, in a magnetic layer that contains a large amount of (A) magnetic powder to the extent that the high relative magnetic permeability required for a magnetic substrate can be achieved, the distance between the particles of the (A-1) alloy powder in the (A) magnetic powder is relatively close. In this way, when a sufficient voltage is applied, the insulation breakdown of the resin component occurs, and current can flow between the particles of the (A-1) alloy powder. In addition, if there is a portion in the magnetic layer where the particles of the (A-1) alloy powder are in contact with each other, a conductive path can be formed by the particles of these (A-1) alloy powders, and current can flow through the conductive path. When current flows, metal ions are reduced on the surface of the particles of the alloy powder (A-1) through which current flows, and the metal can be precipitated. Therefore, electroplating can be performed with the magnetic layer functioning as a cathode, and formation of a plated layer without electroless plating becomes possible.
[0018] The manufacturing method involved in this embodiment may include a step (LF) of forming a resin composition layer containing a resin composition before step (EP), and a step (CU) of curing the resin composition layer to form a magnetic layer. Therefore, the manufacturing method involved in this embodiment may include the following steps in sequence: a step (LF) of forming a resin composition layer, a step (CU) of curing the resin composition layer to form a magnetic layer, and a step (EP) of forming an electroplated layer on the surface of the magnetic layer by electroplating. In this case, the manufacturing method involved in this embodiment does not include a step of forming a conductor layer on the surface of the magnetic layer by a method other than electroplating between step (CU) and step (EP), and a magnetic substrate can be manufactured.
[0019] [Resin composition] The resin composition used in the method for producing a magnetic substrate according to one embodiment of the present invention is described. The resin composition according to this embodiment includes (A) magnetic powder and (B) thermosetting resin. In addition, the resin composition may include any component in combination with (A) magnetic powder and (B) thermosetting resin.
[0020] <(A) Magnetic Powder> The resin composition involved in this embodiment contains (A) magnetic powder as (A) component. (A) Magnetic powder can be particles of a material having a relative magnetic permeability greater than 1. The material of (A) magnetic powder is usually an inorganic material, and can be a soft magnetic material or a hard magnetic material. In addition, the material of (A) magnetic powder can be used alone or in combination of two or more. Therefore, (A) magnetic powder can be soft magnetic powder, hard magnetic powder, or a combination of soft magnetic powder and hard magnetic powder. Among them, (A) magnetic powder preferably contains soft magnetic powder, and more preferably contains only soft magnetic powder. In addition, (A) magnetic powder can be used alone or in combination of two or more.
[0021] (A) Magnetic powder includes (A-1) alloy powder. The (A-1) alloy powder as the (A-1) component is alloy particles. Examples of (A-1) alloy powders include Fe-Si alloy powders, Fe-Si-Al alloy powders, Fe-Cr alloy powders, Fe-Cr-Si alloy powders, Fe-Ni-Cr alloy powders, Fe-Cr-Al alloy powders, Fe-Ni alloy powders, Fe-Ni-Si alloy powders, Fe-Ni-B alloy powders, Fe-Ni-Mo alloy powders, Fe-Ni-Mo-Cu alloy powders, Fe-Co alloy powders, Fe-Ni-Co alloy powders, Co-based amorphous alloy powders, etc. The alloy contained in the (A-1) alloy powder may be crystalline, amorphous, or a combination thereof.
[0022] Among them, as the (A-1) alloy powder, an iron alloy powder as particles of an alloy containing iron is more preferred. Among the iron alloy powders, an iron alloy powder containing the Fe element and at least one element selected from Ni, Cr and Si is more preferred, and one or more selected from Fe-Ni alloy powders, Fe-Cr-Si alloy powders and Fe-Ni-Cr alloy powders are particularly preferred. Fe-Ni alloy powders refer to alloy powders containing Fe and Ni. In addition, Fe-Cr-Si alloy powders refer to alloy powders containing Fe, Cr and Si. Furthermore, Fe-Ni-Cr alloy powders refer to alloy powders containing Fe, Ni and Cr. When these preferred (A-1) alloy powders are used, a magnetic layer with excellent magnetic properties can be obtained, and a plated layer can be smoothly formed on the surface of the magnetic layer by electroplating.
[0023] As the (A-1) alloy powder, a commercially available product can be used. Examples of commercially available (A-1) alloy powders include "AKT-PB (5)" (Fe-Ni alloy powder) and "AKT-PB-3Si (5)" (Fe-Ni-Si alloy powder) manufactured by Mitsubishi Steel Corporation; "CVD iron powder" (Fe-Cr-Si alloy powder) manufactured by JFE Mineral; "AW2-08 PF3F" (Fe-Si-Cr alloy powder) manufactured by Epson Atmix; "MA-RCO-5" (Fe-Ni-B alloy) and "MA-RCO-24" (Fe-Ni alloy) manufactured by DOWA Electronics.
[0024] The (A-1) alloy powder may be used alone or in combination of two or more.
[0025] The (A-1) alloy powder preferably has an average particle size within a specific range. The average particle size of the (A-1) alloy powder is preferably in the range of 0.001 μm or more, more preferably 0.01 μm or more, further preferably 0.1 μm or more, preferably 800 μm or less, more preferably 300 μm or less, further preferably 100 μm or less. When the (A-1) alloy powder having an average particle size within this range is used, a magnetic layer having excellent magnetic properties can be obtained, and an electroplated layer can be smoothly formed on the surface of the magnetic layer by electroplating.
[0026] Unless otherwise stated, the average particle size represents the median particle size on a volume basis. The average particle size can be measured by a laser diffraction / scattering method based on Mie scattering theory. Specifically, a particle size distribution is prepared on a volume basis using a laser diffraction scattering particle size distribution measuring device, and the median particle size can be measured as the average particle size. The sample to be measured can preferably be a sample obtained by dispersing the powder in water using ultrasound. As a laser diffraction scattering particle size distribution measuring device, "LA-500" manufactured by Horiba, Ltd., "SALD-2200" manufactured by Shimadzu Corporation, etc. can be used.
[0027] From the viewpoint of improving relative magnetic permeability, the specific surface area of the alloy powder (A-1) is preferably 0.05 m 2 / g or more, more preferably 0.1m 2 / g or more, more preferably 0.3m 2 / g or more, preferably 10m 2 / g or less, more preferably 8m 2 / g or less, more preferably 5m 2 / g or less. (A-1) The specific surface area of the alloy powder can be measured by the BET method. Specifically, the specific surface area can be measured by the BET multipoint method using a specific surface area measuring device ("Macsorb HM Model 1210" manufactured by Mountech) by adsorbing nitrogen on the sample surface.
[0028] The particles of the (A-1) alloy powder are preferably spherical or ellipsoidal particles. The ratio (aspect ratio) calculated by dividing the length of the major axis of the particles of the (A-1) alloy powder by the length of the minor axis is preferably in the range of 2 or less, more preferably 1.5 or less, further preferably 1.2 or less, and usually 1.0 or more. Generally speaking, if the shape of the particles of the magnetic powder is a non-spherical flat shape, it is easy to improve the relative magnetic permeability. On the other hand, if the shape of the particles of the magnetic powder is close to spherical, it is easy to reduce the magnetic loss.
[0029] (A-1) The true specific gravity of the alloy powder may be, for example, 4 g / cm 3~10g / cm 3 .
[0030] The (A) magnetic powder contains a specific range of amounts of the (A-1) alloy powder. The specific amount (mass %) of the (A-1) alloy powder is generally 30% by mass or more, preferably 40% by mass or more, more preferably 50% by mass or more, and may be 60% by mass or more, relative to 100% by mass of the (A) magnetic powder. The upper limit is generally 100% by mass or less. When using the (A-1) alloy powder in this range, an electroplating layer can be formed on the surface of the magnetic layer by electroplating. In addition, a magnetic layer having excellent magnetic properties can generally be obtained. Furthermore, preferably, the smoothness of the surface of the electroplated layer formed can be improved.
[0031] The amount (volume %) of the (A-1) alloy powder is preferably 20% by volume or more, more preferably 30% by volume or more, further preferably 40% by volume or more, and may be 50% by volume or more, relative to 100% by volume of the (A) magnetic powder. The upper limit is usually 100% by volume or less. When the (A-1) alloy powder in the amount of this range is used, a magnetic layer having excellent magnetic properties can be obtained, and an electroplated layer can be smoothly formed on the surface of the magnetic layer by electroplating. Furthermore, preferably, the smoothness of the surface of the electroplated layer formed can be improved.
[0032] The volume-based amount (volume %) of each component contained in the resin composition is calculated from the mass of the components contained in the resin composition. Specifically, the volume of each component can be obtained by dividing the mass by the specific gravity, and the volume-based amount (volume %) can be calculated based on the volume of each component thus obtained.
[0033] The amount (mass %) of the (A-1) alloy powder is preferably 10% by mass or more, more preferably 15% by mass or more, further preferably 20% by mass or more, preferably 99% by mass or less, more preferably 98% by mass or less, and further preferably 97% by mass or less, relative to 100% by mass of the non-volatile component of the resin composition. When the (A-1) alloy powder in the amount of this range is used, a magnetic layer having excellent magnetic properties can be obtained, and an electroplated layer can be smoothly formed on the surface of the magnetic layer by electroplating. Furthermore, preferably, the smoothness of the surface of the formed electroplated layer can be improved.
[0034] The amount (volume %) of the (A-1) alloy powder is preferably 10% by volume or more, more preferably 13% by volume or more, further preferably 16% by volume or more, preferably 90% by volume or less, more preferably 85% by volume or less, and further preferably 80% by volume or less, relative to 100% by volume of the non-volatile component of the resin composition. When the (A-1) alloy powder in the amount of this range is used, a magnetic layer having excellent magnetic properties can be obtained, and an electroplated layer can be smoothly formed on the surface of the magnetic layer by electroplating. Furthermore, preferably, the smoothness of the surface of the formed electroplated layer can be improved.
[0035] (A) The magnetic powder may include any magnetic powder (A-2) other than the alloy powder (A-1). Examples of the magnetic powder (A-2) include magnetic metal oxide powder and magnetic metal powder other than the alloy powder (A-1).
[0036] Examples of the magnetic metal oxide powder include ferrite powders such as Fe-Mn ferrite powder, Fe-Mn-Mg ferrite powder, Fe-Mn-Mg-Sr ferrite powder, Fe-Mg-Zn ferrite powder, Fe-Mg-Sr ferrite powder, Fe-Zn-Mn ferrite powder, Fe-Cu-Zn ferrite powder, Fe-Ni-Zn ferrite powder, Fe-Ni-Zn-Cu ferrite powder, Fe-Ba-Zn ferrite powder, Fe-Ba-Mg ferrite powder, Fe-Ba-Ni ferrite powder, Fe-Ba-Co ferrite powder, Fe-Ba-Ni-Co ferrite powder, and Fe-Y ferrite powder; and iron oxide powders such as iron (III) oxide powder and iron oxide powder.
[0037] Examples of magnetic metal powders other than the (A-1) alloy powder include pure iron powder and the like.
[0038] Among any magnetic powders in (A-2), magnetic metal oxide powders are preferred, and ferrite powders are more preferred. Ferrite powders are usually formed of composite oxides with iron oxide as the main component and are chemically stable. Therefore, according to the ferrite powder, advantages such as high corrosion resistance, low risk of fire, and difficulty in demagnetization can be obtained. Among them, ferrite powders containing at least one element selected from Mn and Zn are preferred, ferrite powders containing Mn are more preferred, and Fe-Mn ferrite powders and Fe-Mn-Zn ferrite powders are particularly preferred. Fe-Mn ferrite powders refer to ferrite powders containing Fe and Mn, and Fe-Mn-Zn ferrite powders refer to ferrite powders containing Fe, Mn and Zn.
[0039] As the arbitrary magnetic powder (A-2), a commercially available product can be used. Examples of the commercially available arbitrary magnetic powder (A-2) include "M001", "M03S", "M05S", "MZ03S", and "MZ05S" manufactured by Powdertech; "AW2-08" manufactured by Epson Atmix; "LD-M", "LD-MH", "KNI-106", "KNI-106GSM", "KNI-106GS", "KNI-109", and "KNI-109GSM" manufactured by JFE Chemical; and "KNS-415", "BSF-547", "BSF-029", "BSN-125", "BSN-714", and "BSN-828" manufactured by Toda Industries, Ltd.
[0040] (A-2) Any magnetic powder may be used alone or in combination of two or more.
[0041] The average particle size of the arbitrary magnetic powder (A-2) is not particularly limited. The average particle size of the arbitrary magnetic powder (A-2) is preferably smaller than the average particle size of the alloy powder (A-1). The arbitrary magnetic powder (A-2) that is smaller than the alloy powder (A-1) can enter the gaps between the particles of the alloy powder (A-1). Therefore, the packing density of the magnetic powder (A) as the magnetic layer as a whole can be increased, so the magnetic properties can be made particularly good. In addition, according to such a small arbitrary magnetic powder (A-2), the distance between the particles of the alloy powder (A-1) can be suppressed from expanding due to the exclusion volume of the particles of the arbitrary magnetic powder (A-2), so that the flow of current during electroplating can be smooth and the electroplating layer can be effectively formed. The specific range of the average particle size of the arbitrary magnetic powder (A-2) is preferably 0.001 μm or more, more preferably 0.01 μm or more, and further preferably 0.1 μm or more, preferably 500 μm or less, more preferably 100 μm or less, and further preferably 50 μm or less.
[0042] The specific surface area of the arbitrary magnetic powder (A-2) is not particularly limited. From the viewpoint of improving relative magnetic permeability, the specific surface area of the arbitrary magnetic powder (A-2) is preferably in the same range as the specific surface area of the alloy powder (A-1).
[0043] The shape of the arbitrary magnetic powder (A-2) is not particularly limited. For example, the arbitrary magnetic powder (A-2) may have the same shape as the particles of the alloy powder (A-1). Therefore, the range of the aspect ratio of the particles of the arbitrary magnetic powder (A-2) may be the same as the range of the aspect ratio of the particles of the alloy powder (A-1).
[0044] The true specific gravity of the arbitrary magnetic powder (A-2) is not particularly limited. For example, the true specific gravity of the arbitrary magnetic powder (A-2) may be in the same range as the true specific gravity of the alloy powder (A-1).
[0045] The range of the amount (mass %) of the (A) magnetic powder is preferably 60% by mass or more, more preferably 70% by mass or more, further preferably 80% by mass or more, preferably 99% by mass or less, more preferably 98% by mass or less, and further preferably 97% by mass or less, relative to 100% by mass of the non-volatile component of the resin composition. In the case where the amount of the (A) magnetic powder as a whole comprising (A-1) alloy powder and (A-2) any magnetic powder is within the above range, a magnetic layer with excellent magnetic properties can be obtained, and an electroplating layer can be smoothly formed on the surface of the magnetic layer by electroplating. In particular, from the viewpoint of improving the smoothness of the electroplating layer, the amount (mass %) of the (A) magnetic powder is preferably 85% by mass or more. In the case where the amount of the (A) magnetic powder is so much, the (A-1) alloy powder, which is the starting point for the precipitation of metal ions used to form the electroplating layer, can be densely distributed, so that the deviation of the precipitation degree can be suppressed, and a smooth electroplating layer can be effectively obtained.
[0046] Relative to 100% by volume of the non-volatile component of the resin composition, the range of the amount (volume %) of the (A) magnetic powder is preferably 30% by volume or more, more preferably 40% by volume or more, further preferably 50% by volume or more, preferably 90% by volume or less, more preferably 85% by volume or less, and further preferably 80% by volume or less. When the amount of the (A) magnetic powder as a whole comprising (A-1) alloy powder and (A-2) any magnetic powder is within the above range, a magnetic layer with excellent magnetic properties can be obtained, and an electroplating layer can be smoothly formed on the surface of the magnetic layer by electroplating. In particular, from the viewpoint of improving the smoothness of the electroplating layer, the amount (volume %) of the (A) magnetic powder is preferably 55% by volume or more. In the case of so much amount of the (A) magnetic powder, the (A-1) alloy powder, which is the starting point for the precipitation of metal ions used to form the electroplating layer, can be densely distributed, so that the deviation of the precipitation degree can be suppressed, and a smooth electroplating layer can be effectively obtained.
[0047] <(B) Thermosetting resin> The resin composition involved in this embodiment includes (B) thermosetting resin as (B) component. (B) Thermosetting resin is usually able to bond (A) magnetic powder. In addition, (B) thermosetting resin reacts with heat to produce bonding (bonding), which can cure the resin composition. Therefore, the resin composition comprising (A) magnetic powder and (B) thermosetting resin can be cured to form a cured product. Moreover, a magnetic layer can be formed using the cured product.
[0048] Examples of the thermosetting resin (B) include epoxy resins, phenolic resins, active ester resins, amine resins, acid anhydride resins, benzoxazine resins, cyanate resins, and carbodiimide resins. The thermosetting resin (B) may be used alone or in combination of two or more.
[0049] (B) Thermosetting resin preferably includes (B-1) epoxy resin. (B-1) Epoxy resin refers to a resin having one or more epoxy groups in the molecule. Examples of (B-1) epoxy resin include: biphenyl type epoxy resin; bisphenol A type epoxy resin; bisphenol F type epoxy resin; bisphenol S type epoxy resin; bisphenol AF type epoxy resin; dicyclopentadiene type epoxy resin; trisphenol type epoxy resin; phenol novolac type epoxy resin; glycidylamine type epoxy resin; glycidyl ester type epoxy resin; cresol novolac type epoxy resin; biphenyl type epoxy resin; linear aliphatic epoxy resin; epoxy resin having a butadiene structure; alicyclic epoxy resin; alicyclic epoxy resin having an ester skeleton; The epoxy resins include epoxy resins of the group consisting of ...
[0050] The epoxy resin (B-1) preferably contains an epoxy resin having two or more epoxy groups in one molecule. The proportion of the epoxy resin having two or more epoxy groups in one molecule is preferably 50% by mass or more, more preferably 60% by mass or more, and even more preferably 70% by mass or more, relative to 100% by mass of the total amount of the epoxy resin (B-1).
[0051] (B-1) The epoxy resin preferably has an aromatic structure. When two or more epoxy resins are used, preferably one or more epoxy resins have an aromatic structure. The aromatic structure is a chemical structure generally defined as an aromatic structure, and also includes polycyclic aromatics and aromatic heterocycles.
[0052] The epoxy resin (B-1) includes an epoxy resin that is liquid at 20°C (hereinafter sometimes referred to as "liquid epoxy resin") and an epoxy resin that is solid at 20°C (hereinafter sometimes referred to as "solid epoxy resin"). The epoxy resin (B-1) may be only a liquid epoxy resin, only a solid epoxy resin, or a combination of a liquid epoxy resin and a solid epoxy resin. Among them, the epoxy resin (B-1) preferably includes a liquid epoxy resin, and particularly preferably includes only a liquid epoxy resin.
[0053] As the liquid epoxy resin, a liquid epoxy resin having more than two epoxy groups in one molecule is preferred. As the liquid epoxy resin, bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol AF type epoxy resin, naphthalene type epoxy resin, glycidyl ester type epoxy resin, glycidyl amine type epoxy resin, phenol novolac type epoxy resin, alicyclic epoxy resin with ester skeleton, cyclohexane type epoxy resin, cyclohexanedimethanol type epoxy resin, epoxy resin with butadiene structure, epoxy resin containing alkylene oxide skeleton and butadiene skeleton, epoxy resin containing fluorene structure, dicyclopentadiene type epoxy resin are preferred. Among them, bisphenol A type epoxy resin, bisphenol F type epoxy resin, glycidyl amine type epoxy resin and cyclohexane type epoxy resin are particularly preferred.
[0054] Specific examples of liquid epoxy resins include: "YX7400" manufactured by Mitsubishi Chemical Corporation; "HP4032", "HP4032D", and "HP4032SS" (naphthalene-type epoxy resins) manufactured by DIC Corporation; "828US", "828EL", "jER828EL", "825", and "EPIKOTE "828EL" (bisphenol A type epoxy resin); "jER807", "1750" (bisphenol F type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "jER152" (phenol novolac type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "630", "630LSD", "604" (glycidylamine type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "ED-523T" (GLYCIROL type epoxy resin) manufactured by ADEKA Corporation; "EP-3950L", "EP-3980S" (glycidylamine type epoxy resin) manufactured by ADEKA Corporation; "EP-4088S" (dicyclopentadiene type epoxy resin) manufactured by ADEKA Corporation; "ZX-1059" (a mixture of bisphenol A type epoxy resin and bisphenol F type epoxy resin) manufactured by Nippon Steel Chemical Materials Co., Ltd.; Nagase "EX-721" (glycidyl ester type epoxy resin) manufactured by ChemteX; "EX-991L" (epoxy resin containing an alkylene oxide skeleton) manufactured by Nagase ChemteX; "CELLOXIDE 2021P" and "CELLOXIDE 2081" (alicyclic epoxy resins having an ester skeleton) manufactured by Daicel; "PB-3600" manufactured by Daicel, "JP-100" and "JP-200" manufactured by Nippon Soda Co., Ltd. (epoxy resins having a butadiene structure); "ZX1658" and "ZX1658GS" (liquid 1,4-glycidylcyclohexane type epoxy resins) manufactured by Nippon Steel Chemicals Co., Ltd.; "EG-280" (epoxy resin containing a fluorene structure) manufactured by Osaka Gas Chemical Co., Ltd., etc. The liquid epoxy resins may be used alone or in combination of two or more.
[0055] As the solid epoxy resin, a solid epoxy resin having three or more epoxy groups in one molecule is preferred, and an aromatic solid epoxy resin having three or more epoxy groups in one molecule is more preferred. As the solid epoxy resin, a biphenylol type epoxy resin, a naphthalene type epoxy resin, a naphthalene type tetrafunctional epoxy resin, a cresol novolac type epoxy resin, a dicyclopentadiene type epoxy resin, a trisphenol type epoxy resin, a naphthol type epoxy resin, a biphenyl type epoxy resin, a naphthyl ether type epoxy resin, anthracene type epoxy resin, a bisphenol A type epoxy resin, a bisphenol AF type epoxy resin, a tetraphenylethane type epoxy resin is preferred, and a dicyclopentadiene type epoxy resin is particularly preferred.
[0056] Specific examples of solid epoxy resins include "HP4032H" (naphthalene-type epoxy resin) manufactured by DIC Corporation; "HP-4700" and "HP-4710" (naphthalene-type tetrafunctional epoxy resin) manufactured by DIC Corporation; "N-690" (cresol novolac-type epoxy resin) manufactured by DIC Corporation; "N-695" (cresol novolac-type epoxy resin) manufactured by DIC Corporation; "HP-7200", "HP-7200HH", and "HP-7200H" (dicyclopentadiene epoxy resin) manufactured by DIC Corporation; "EXA-7311", "EXA-7311-G3", "EXA-7311-G4", "EXA-7311-G4S", "HP6000" (naphthylene ether type epoxy resin) manufactured by DIC Corporation; "EPPN-502H" (trisphenol type epoxy resin) manufactured by Nippon Kayaku Co., Ltd.; "NC7000L" (naphthol novolac type epoxy resin) manufactured by Nippon Kayaku Co., Ltd.; "NC3000H", "NC3000", "NC3000" manufactured by Nippon Kayaku Co., Ltd. 0L", "NC3100" (biphenyl type epoxy resin); "ESN475V" (naphthol type epoxy resin) manufactured by Nippon Steel Chemical Materials Co., Ltd.; "ESN485" (naphthol novolac type epoxy resin) manufactured by Nippon Steel Chemical Materials Co., Ltd.; "YL6121" (biphenyl type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "YX4000H", "YX4000", "YX4000HK" (biphenyl type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "YX8800" (anthracene type epoxy resin) manufactured by Mitsubishi Chemical Corporation ); "YX7700" manufactured by Mitsubishi Chemical Corporation (a novolac epoxy resin containing a xylene structure); "PG-100" and "CG-500" manufactured by Osaka Gas Chemical Co., Ltd.; "YL7760" manufactured by Mitsubishi Chemical Corporation (a bisphenol AF epoxy resin); "YL7800" manufactured by Mitsubishi Chemical Corporation (a fluorene epoxy resin); "jER1010" manufactured by Mitsubishi Chemical Corporation (a solid bisphenol A epoxy resin); "jER1031S" manufactured by Mitsubishi Chemical Corporation (a tetraphenylethane epoxy resin), etc. Solid epoxy resins can be used alone or in combination of two or more.
[0057] When a liquid epoxy resin and a solid epoxy resin are used in combination as the epoxy resin, the mass ratio of the liquid epoxy resin to the solid epoxy resin (liquid epoxy resin / solid epoxy resin) is preferably 0.5 or more, more preferably 1 or more, further preferably 5 or more, and further preferably 10 or more.
[0058] The epoxy equivalent of the epoxy resin (B-1) is preferably 50 g / eq. to 5000 g / eq., more preferably 60 g / eq. to 3000 g / eq., further preferably 80 g / eq. to 2000 g / eq., and further more preferably 110 g / eq. to 1000 g / eq. The epoxy equivalent is the mass of the resin containing one equivalent of epoxy groups. The epoxy equivalent can be measured according to JIS K 7236.
[0059] The weight average molecular weight (Mw) of the (B-1) epoxy resin is preferably 100 to 5000, more preferably 250 to 3000, and even more preferably 400 to 1500. The weight average molecular weight of the resin can be measured as a value in terms of polystyrene by gel permeation chromatography (GPC).
[0060] The amount (mass %) of the epoxy resin (B-1) contained in the resin composition is preferably 0.1 mass % or more, more preferably 0.5 mass % or more, further preferably 1 mass % or more, and preferably 20 mass % or less, more preferably 15 mass % or less, further preferably 10 mass % or less, relative to 100 mass % of the non-volatile components of the resin composition. When the amount of the epoxy resin (B-1) is within the above range, a magnetic layer having excellent magnetic properties can be obtained, and a plated layer can be smoothly formed on the surface of the magnetic layer by electroplating.
[0061] The amount (mass %) of the epoxy resin (B-1) contained in the resin composition is preferably 10 mass % or more, more preferably 20 mass % or more, and further preferably 30 mass % or more, and preferably 96 mass % or less, more preferably 93 mass % or less, and further preferably 90 mass % or less, relative to 100 mass % of the resin component of the resin composition. When the amount of the epoxy resin (B-1) is within the above range, a magnetic layer having excellent magnetic properties can be obtained, and a plated layer can be smoothly formed on the surface of the magnetic layer by electroplating.
[0062] The amount (mass %) of the epoxy resin (B-1) contained in the resin composition is preferably 0.1 mass % or more, more preferably 0.5 mass % or more, and further preferably 1 mass % or more, and preferably 20 mass % or less, more preferably 16 mass % or less, and further preferably 12 mass % or less, relative to 100 mass % of the magnetic powder (A). When the amount of the epoxy resin (B-1) is within the above range, a magnetic layer having excellent magnetic properties can be obtained, and a plated layer can be smoothly formed on the surface of the magnetic layer by electroplating.
[0063] When (B) thermosetting resin includes (B-1) epoxy resin, (B) thermosetting resin preferably includes a resin that can react and combine with (B-1) epoxy resin. Hereinafter, the resin that can react and combine with (B-1) epoxy resin is sometimes referred to as "(B-2) curing agent". Examples of (B-2) curing agent include phenolic resins, active ester resins, amine resins, carbodiimide resins, anhydride resins, benzoxazine resins, cyanate resins, thiol resins, and the like. (B-2) curing agent can be used alone or in combination of two or more. Among them, phenolic resins are preferred.
[0064] As the phenolic resin, a resin having one or more, preferably two or more, hydroxyl groups bonded to aromatic rings such as a benzene ring and a naphthalene ring in one molecule can be used. From the viewpoint of heat resistance and water resistance, a phenolic resin having a phenolic structure is preferred. In addition, from the viewpoint of close adhesion, a nitrogen-containing phenolic resin is preferred, and a phenolic resin containing a triazine skeleton is more preferred. Among them, from the viewpoint of highly satisfying heat resistance, water resistance and close adhesion, a linear phenolic resin containing a triazine skeleton is preferred.
[0065] Specific examples of phenolic resins include: "MEH-7700", "MEH-7810", "MEH-7851", and "MEH-8000H" manufactured by Meiwa Chemicals; "NHN", "CBN", and "GPH" manufactured by Nippon Kayaku Co., Ltd.; "SN-170", "SN-180", "SN-190", "SN-475", "SN-485", "SN-495", "SN-495V", "SN-375", and "SN-475" manufactured by Nippon Steel Chemicals Co., Ltd. N-395"; "TD-2090", "TD-2090-60M", "LA-7052", "LA-7054", "LA-1356", "LA-3018", "LA-3018-50P", "EXB-9500", "HPC-9500", "KA-1160", "KA-1163", "KA-1165" manufactured by DIC Corporation; "GDP-6115L", "GDP-6115H", "ELPC 75" and other products manufactured by Qun Rong Chemical Co., Ltd.
[0066] As active ester resin, a compound having more than one, preferably more than two active ester groups in one molecule can be used. Among them, as active ester resin, preferably phenolic esters, thiophenolic esters, N-hydroxylamine esters, esters of heterocyclic hydroxy compounds, etc., have more than two reactive ester groups in one molecule. The active ester resin is preferably obtained by the condensation reaction of carboxylic acid compounds and / or thiocarboxylic acid compounds with hydroxy compounds and / or thiol compounds. In particular, from the viewpoint of improving heat resistance, active ester resins obtained from carboxylic acid compounds and hydroxy compounds are preferably obtained, and active ester resins obtained from carboxylic acid compounds and phenolic compounds and / or naphthol compounds are more preferably obtained. As carboxylic acid compounds, for example benzoic acid, acetic acid, succinic acid, maleic acid, itaconic acid, phthalic acid, isophthalic acid, terephthalic acid, pyromellitic acid, etc. can be cited. Examples of the phenol compound or naphthol compound include hydroquinone, resorcinol, bisphenol A, bisphenol F, bisphenol S, phenolphthalein, methylated bisphenol A, methylated bisphenol F, methylated bisphenol S, phenol, o-cresol, m-cresol, p-cresol, catechol, α-naphthol, β-naphthol, 1,5-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 2,6-dihydroxynaphthalene, dihydroxybenzophenone, trihydroxybenzophenone, tetrahydroxybenzophenone, phloroglucinol, pyrogallol, dicyclopentadiene-type diphenol compounds, and novolac resins. Here, the “dicyclopentadiene-type diphenol compound” refers to a diphenol compound obtained by condensing two molecules of phenol with one molecule of dicyclopentadiene.
[0067] Preferred specific examples of active ester resins include active ester resins containing a dicyclopentadiene diphenol structure, active ester resins containing a naphthalene structure, active ester resins containing acetylated products of novolac resins, and active ester resins containing benzoylated products of novolac resins. Among them, active ester resins containing a naphthalene structure and active ester resins containing a dicyclopentadiene diphenol structure are more preferred. "Dicyclopentadiene diphenol structure" means a divalent structural unit formed of phenylene-dicyclopentylene-phenylene.
[0068] As commercially available active ester resins, examples of active ester resins containing a dicyclopentadiene-type diphenol structure include "EXB9451", "EXB9460", "EXB9460S", "HPC-8000-65T", "HPC-8000H-65TM", and "EXB-8000L-65TM" (manufactured by DIC Corporation); examples of active ester resins containing a naphthalene structure include "EXB-9416-70BK", "EXB-8150-65T", "EXB-8100L-65T", and "EXB-8150L-65T" (manufactured by DIC Corporation) ; As the active ester resin containing an acetylated product of a linear phenolic resin, "DC808" (manufactured by Mitsubishi Chemical Corporation) can be mentioned; as the active ester resin containing a benzoylated product of a linear phenolic resin, "YLH1026" (manufactured by Mitsubishi Chemical Corporation) can be mentioned; as the active ester resin which is an acetylated product of a linear phenolic resin, "DC808" (manufactured by Mitsubishi Chemical Corporation) can be mentioned; as the active ester resin which is a benzoylated product of a linear phenolic resin, "YLH1026" (manufactured by Mitsubishi Chemical Corporation), "YLH1030" (manufactured by Mitsubishi Chemical Corporation), "YLH1048" (manufactured by Mitsubishi Chemical Corporation) and the like can be mentioned.
[0069] As the amine resin, a resin having one or more, preferably two or more, amino groups in one molecule can be used. As the amine resin, for example, aliphatic amines, polyether amines, alicyclic amines, aromatic amines, etc. can be mentioned, among which aromatic amines are preferred. The amine resin is preferably a primary amine or a secondary amine, and more preferably a primary amine. Specific examples of the amine resin include 4,4'-methylenebis(2,6-dimethylaniline), diphenyldiaminosulfone, 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenylsulfone, 3,3'-diaminodiphenylsulfone, metaphenylenediamine, metaphenylenediamine, diethyltoluenediamine, 4,4'-diaminodiphenyl ether, 3,3'-dimethyl-4,4'-diaminobiphenyl, 2,2'-dimethyl-4,4'-diaminobiphenyl, 3,3'-dihydroxybenzidine, 2,2-bis(3-amino-4 4-(4-aminophenoxy)phenyl)propane, 1,3-bis(3-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, 4,4'-bis(4-aminophenoxy)biphenyl, bis(4-(4-aminophenoxy)phenyl)sulfone, bis(4-(3-aminophenoxy)phenyl)sulfone, etc. Examples of commercially available amine resins include "KAYABOND C-200S", "KAYABOND C-100", "KAYAHARD AA", "KAYAHARD AB", "KAYAHARD AS" manufactured by Nippon Kayaku Co., Ltd., and "Epicure W" manufactured by Mitsubishi Chemical Corporation.
[0070] As the carbodiimide resin, a compound having one or more, preferably two or more, carbodiimide structures in one molecule can be used. Specific examples of the carbodiimide resin include: aliphatic biscarbodiimides such as tetramethylene-bis(tert-butylcarbodiimide) and cyclohexanebis(methylene-tert-butylcarbodiimide); aromatic biscarbodiimides such as phenylene-bis(xylylcarbodiimide); aliphatic polycarbodiimides such as polyhexamethylenecarbodiimide, polytrimethylhexamethylenecarbodiimide, polycyclohexylenecarbodiimide, poly(methylenebiscyclohexylenecarbodiimide), poly(isophoronecarbodiimide); poly(phenylenecarbodiimide), poly Aromatic polycarbodiimides such as poly(naphthylene carbodiimide), poly(tolylene carbodiimide), poly(methyl diisopropyl phenylene carbodiimide), poly(triethyl phenylene carbodiimide), poly(diethyl phenylene carbodiimide), poly(triisopropyl phenylene carbodiimide), poly(diisopropyl phenylene carbodiimide), poly(xylylene carbodiimide), poly(tetramethyl xylylene carbodiimide), poly(methylene diphenylene carbodiimide), poly[methylene bis(methyl phenylene) carbodiimide], etc. Examples of commercially available carbodiimide resins include "CARBODILITE V-02B", "CARBODILITE V-03", "CARBODILITE V-04K", "CARBODILITE V-07" and "CARBODILITE V-09" manufactured by Nisshinbo Chemical Co., Ltd. and "Stabaxol P", "Stabaxol P400" and "Hycasyl 510" manufactured by Rhein Chemie.
[0071] As the acid anhydride resin, a resin having one or more acid anhydride groups in one molecule can be used, preferably a resin having two or more acid anhydride groups in one molecule. Specific examples of the acid anhydride resin include phthalic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, methylnadic anhydride, hydrogenated methylnadic anhydride, trialkyltetrahydrophthalic anhydride, dodecenylsuccinic anhydride, 5-(2,5-dioxotetrahydro-3-furanyl)-3-methyl-3-cyclohexene-1,2-dicarboxylic anhydride, trimellitic anhydride, pyromellitic anhydride, Polymer-type acid anhydrides such as benzophenonetetracarboxylic dianhydride, biphenyltetracarboxylic dianhydride, naphthalenetetracarboxylic dianhydride, oxydiphthalic dianhydride, 3,3'-4,4'-diphenylsulfonetetracarboxylic dianhydride, 1,3,3a,4,5,9b-hexahydro-5-(tetrahydro-2,5-dioxo-3-furanyl)-naphtho[1,2-c]furan-1,3-dione, ethylene glycol bis(trimellitic anhydride), and styrene-maleic acid resin obtained by copolymerizing styrene with maleic acid. Commercially available products of the acid anhydride resin include, for example, "HNA-100", "MH-700", "MTA-15", "DDSA", and "OSA" manufactured by Shin Nippon Rika Co., Ltd., "YH-306" and "YH-307" manufactured by Mitsubishi Chemical Corporation, "HN-2200" and "HN-5500" manufactured by Hitachi Chemical Co., Ltd., and "EF-30", "EF-40", "EF-60", and "EF-80" manufactured by Cray Valley Corporation.
[0072] Specific examples of the benzoxazine resin include "JBZ-OD100", "JBZ-OP100D", and "ODA-BOZ" manufactured by JFE Chemical Co., Ltd.; "Pd" and "Fa" manufactured by Shikoku Chemical Industry Co., Ltd.; and "HFB2006M" manufactured by Showa High Molecular Co., Ltd.
[0073] Examples of the cyanate resin include difunctional cyanate resins such as bisphenol A dicyanate, polyphenol cyanate, oligo(3-methylene-1,5-phenylene cyanate), 4,4′-methylenebis(2,6-dimethylphenylcyanate), 4,4′-ethylidene diphenyl dicyanate, hexafluorobisphenol A dicyanate, 2,2-bis(4-cyano)phenylpropane, 1,1-bis(4-cyanophenylmethane), bis(4-cyano-3,5-dimethylphenyl)methane, 1,3-bis(4-cyanophenyl-1-(methylethylidene))benzene, bis(4-cyanophenyl)sulfide and bis(4-cyanophenyl)ether; polyfunctional cyanate resins derived from phenol novolac resins and cresol novolac resins; and prepolymers obtained by triazinization of a portion of these cyanate resins. Specific examples of cyanate ester resins include "PT30" and "PT60" manufactured by Lonza Japan (linear phenolic resin-type multifunctional cyanate ester resins), "ULL-950S" (multifunctional cyanate ester resin), "BA230", "BA230S75" (prepolymers in which part or all of bisphenol A dicyanate is triazine-treated to form a trimer), and the like.
[0074] Examples of the thiol resin include trimethylolpropane tris(3-mercaptopropionate), pentaerythritol tetrakis(3-mercaptobutyrate), and tris(3-mercaptopropyl)isocyanurate.
[0075] The active group equivalent of the curing agent (B-2) is preferably 50 g / eq. to 3000 g / eq., more preferably 100 g / eq. to 1000 g / eq., further preferably 100 g / eq. to 500 g / eq., and more preferably 100 g / eq. to 300 g / eq. The active group equivalent represents the mass of the curing agent (B-2) per 1 equivalent of active groups.
[0077] When the number of epoxy groups of the epoxy resin (B-1) is set to 1, the number of active groups of the curing agent (B-2) is preferably 0.01 or more, more preferably 0.1 or more, further preferably 0.5 or more, preferably 10 or less, more preferably 5 or less, and further preferably 2 or less. The active group of the curing agent (B-2) is an active hydroxyl group, etc., which varies depending on the type of curing agent. In addition, the number of epoxy groups of the epoxy resin (B-1) refers to the value obtained by adding up the values obtained by dividing the mass of the non-volatile components of each epoxy resin by the epoxy equivalent for all epoxy resins. Furthermore, the number of active groups of the curing agent (B-2) refers to the value obtained by adding up the values obtained by dividing the mass of the non-volatile components of each curing agent by the active group equivalent for all curing agents.
[0077] The amount (mass %) of the (B-2) curing agent contained in the resin composition relative to 100 mass % of the non-volatile components of the resin composition is preferably in the range of 0.1 mass % or more, more preferably 0.5 mass % or more, further preferably 1 mass % or more, preferably 15 mass % or less, more preferably 10 mass % or less, further preferably 5 mass % or less.
[0078] The amount (mass %) of the (B-2) curing agent contained in the resin composition relative to 100 mass % of the resin component of the resin composition is preferably in the range of 10 mass % or more, more preferably 20 mass % or more, further preferably 30 mass % or more, preferably 70 mass % or less, more preferably 60 mass % or less, further preferably 50 mass % or less.
[0079] When (B) thermosetting resin is classified by viscosity, (B) thermosetting resin may contain a reactive diluent. Reactive diluent refers to a component with low viscosity in (B) thermosetting resin. The specific viscosity of the reactive diluent is usually less than 0.5 Pa·s. There is no particular restriction on the lower limit of the viscosity of the reactive diluent, for example, it may be above 0.001 Pa·s, above 0.005 Pa·s, above 0.01 Pa·s, etc. The viscosity of the reactive diluent can be measured using an E-type viscometer at 25±2°C. When (B) thermosetting resin contains a reactive diluent, the viscosity of the resin composition can be reduced, so that the coating property of the liquid resin composition such as magnetic paste and magnetic ink can be improved.
[0080] The reactive diluent may contain reactive groups such as the above-mentioned epoxy group and active group. Preferred examples of the reactive groups contained in the reactive diluent include epoxy group, acryloyl group, methacryloyl group, oxetanyl group, etc., among which epoxy group is preferred. Therefore, as the reactive diluent, it is preferred to use (B-1) epoxy resin having low viscosity.
[0081] As commercially available reactive diluents, for example, "EX-201" (cyclic aliphatic glycidyl ether), "EX-830", "EX-821" (ethylene glycol type epoxy resin), "EX-212" (hexanediol type epoxy resin) manufactured by Nippon Steel Chemical Materials Co., Ltd.; "ZX1658", "ZX1658GS" (liquid 1,4-glycidyl cyclohexane); "EP-3980S" (glycidylamine type epoxy resin), "EP-4088S", "EP-4088L" (dicyclopentadiene type epoxy resin), "ED-509S" (tert-butylphenyl glycidyl ether) manufactured by ADEKA; "X-22-163" (siloxane type epoxy resin) manufactured by Shin-Etsu Chemical Co., Ltd., etc. The reactive diluent may be used alone or in combination of two or more.
[0082] The amount (mass %) of the reactive diluent contained in the resin composition relative to 100 mass % of the non-volatile component of the resin composition is preferably 0.1 mass % or more, more preferably 0.5 mass % or more, further preferably 1 mass % or more, preferably 20 mass % or less, more preferably 10 mass % or less, further preferably 7 mass % or less.
[0083] The amount (mass %) of the reactive diluent contained in the resin composition relative to 100 mass % of the resin component of the resin composition is preferably 5 mass % or more, more preferably 10 mass % or more, further preferably 20 mass % or more, preferably 80 mass % or less, more preferably 70 mass % or less, further preferably 60 mass % or less.
[0084] The amount (mass %) of the reactive diluent contained in the resin composition relative to 100 mass % of the (B) thermosetting resin is preferably 5 mass % or more, more preferably 10 mass % or more, further preferably 20 mass % or more, preferably 90 mass % or less, more preferably 80 mass % or less, further preferably 70 mass % or less.
[0085] The weight average molecular weight (Mw) of the (B) thermosetting resin may generally be in the same range as the weight average molecular weight of the (B-1) epoxy resin described above.
[0086] The amount (mass %) of the (B) thermosetting resin contained in the resin composition is preferably 0.1 mass % or more, more preferably 1 mass % or more, further preferably 2 mass % or more, and preferably 15 mass % or less, more preferably 13 mass % or less, further preferably 10 mass % or less, relative to 100 mass % of the non-volatile components of the resin composition. When the amount of the (B) thermosetting resin is within the above range, a magnetic layer having excellent magnetic properties can be obtained, and a plated layer can be smoothly formed on the surface of the magnetic layer by electroplating.
[0087] The amount (mass %) of the (B) thermosetting resin contained in the resin composition is preferably 40 mass % or more, more preferably 50 mass % or more, and further preferably 60 mass % or more, and preferably 98 mass % or less, more preferably 94 mass % or less, and further preferably 90 mass % or less, relative to 100 mass % of the resin component of the resin composition. When the amount of the (B) thermosetting resin is within the above range, a magnetic layer having excellent magnetic properties can be obtained, and a plated layer can be smoothly formed on the surface of the magnetic layer by electroplating.
[0088] The amount (mass %) of the thermosetting resin (B) contained in the resin composition relative to 100 mass % of the magnetic powder (A) is preferably 0.1 mass % or more, more preferably 1 mass % or more, and further preferably 2 mass % or more, and preferably 20 mass % or less, more preferably 16 mass % or less, and further preferably 12 mass % or less. When the amount of the thermosetting resin (B) is within the above range, a magnetic layer having excellent magnetic properties can be obtained, and a plated layer can be smoothly formed on the surface of the magnetic layer by electroplating.
[0089] <(C) Curing Accelerator> The resin composition according to the present embodiment may be combined with the above-mentioned (A) to (B) components and further include a (C) curing accelerator as an arbitrary component. The (C) curing accelerator as the (C) component does not include substances belonging to the above-mentioned (A) to (B) components. The (C) curing accelerator has a function as a catalyst for promoting the curing reaction of the (B) thermosetting resin, and thus can promote the curing of the resin composition.
[0090] Examples of the curing accelerator (C) include phosphorus-based curing accelerators, amine-based curing accelerators, imidazole-based curing accelerators, guanidine-based curing accelerators, and metal-based curing accelerators. Among them, imidazole-based curing accelerators are preferred. The curing accelerator (C) may be used alone or in combination of two or more.
[0091] Examples of the imidazole curing accelerator include 2-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, 1-benzyl-2-phenylimidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazole trimellitate, 1-cyanoethyl-2-phenylimidazole trimellitate, 2,4-diamino-6-[2′-methylimidazolyl-(1′)]-ethyl-s-triazine, 2,4- Imidazole compounds such as diamino-6-[2'-undecylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine isocyanuric acid adduct, 2-phenylimidazole isocyanuric acid adduct, 2-phenyl-4,5-dihydroxymethylimidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole, 2,3-dihydro-1H-pyrrolo[1,2-a]benzimidazole, 1-dodecyl-2-methyl-3-benzylimidazolium chloride, 2-methylimidazoline, 2-phenylimidazoline, and adducts of imidazole compounds with epoxy resins, preferably 2-ethyl-4-methylimidazole and 1-benzyl-2-phenylimidazole. As the imidazole-based curing accelerator, commercially available products can be used, for example, "P200-H50" manufactured by Mitsubishi Chemical Corporation; "Curezol 2MZ", "2E4MZ", "Cl1Z", "Cl1Z-CN", "Cl1Z-CNS", "C11Z-A", "2MZ-OK", "2MA-OK", "2MA-OK-PW", "2MZA-PW", "2PHZ", "2PHZ-PW" and the like manufactured by Shikoku Chemical Industries, Ltd.
[0092] Examples of the amine-based curing accelerator include trialkylamines such as triethylamine and tributylamine, 4-dimethylaminopyridine, benzyldimethylamine, 2,4,6-tris(dimethylaminomethyl)phenol, 1,8-diazabicyclo[5.4.0]undecene, 1,8-diazabicyclo[5.4.0]undecene-7,4-dimethylaminopyridine, and 2,4,6-tris(dimethylaminomethyl)phenol, and 4-dimethylaminopyridine is preferred.
[0093] Examples of the phosphorus-based curing accelerator include triphenylphosphine, phosphonium borate compounds, tetraphenylphosphonium tetraphenylborate, n-butylphosphonium tetraphenylborate, tetrabutylphosphonium decanoate, (4-methylphenyl)triphenylphosphonium thiocyanate, tetraphenylphosphonium thiocyanate, and butyltriphenylphosphonium thiocyanate, and preferably triphenylphosphine and tetrabutylphosphonium decanoate.
[0094] Examples of the guanidine-based curing accelerator include dicyandiamide, 1-methylguanidine, 1-ethylguanidine, 1-cyclohexylguanidine, 1-phenylguanidine, 1-(o-tolyl)guanidine, dimethylguanidine, diphenylguanidine, trimethylguanidine, tetramethylguanidine, pentamethylguanidine, 1,5,7-triazabicyclo[4.4.0]dec-5-ene, 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene, 1-methylbiguanidine, 1-ethylbiguanidine, 1-n-butylbiguanidine, 1-n-octadecylbiguanidine, 1,1-dimethylbiguanidine, 1,1-diethylbiguanidine, 1-cyclohexylbiguanidine, 1-allylbiguanidine, 1-phenylbiguanidine, and 1-(o-tolyl)biguanidine. Preferred examples include dicyandiamide and 1,5,7-triazabicyclo[4.4.0]dec-5-ene.
[0095] As metal curing accelerators, organic metal complexes or organic metal salts of metals such as cobalt, copper, zinc, iron, nickel, manganese, and tin can be cited. Specific examples of organic metal complexes include organic cobalt complexes such as cobalt acetylacetonate (II) and cobalt acetylacetonate (III); organic copper complexes such as copper acetylacetonate (II); organic zinc complexes such as zinc acetylacetonate (II); organic iron complexes such as iron acetylacetonate (III); organic nickel complexes such as nickel acetylacetonate (II); organic manganese complexes such as manganese acetylacetonate (II). As organic metal salts, for example, zinc octylate, tin octylate, zinc naphthenate, cobalt naphthenate, tin stearate, zinc stearate, etc. can be cited.
[0096] The amount (mass %) of the (C) curing accelerator contained in the resin composition relative to 100 mass % of the non-volatile components of the resin composition can be 0 mass % or greater than 0 mass %, preferably 0.001 mass % or more, more preferably 0.01 mass % or more, further preferably 0.1 mass % or more, preferably 5 mass % or less, more preferably 3 mass % or less, further preferably 1 mass % or less.
[0097] The amount (mass %) of the (C) curing accelerator contained in the resin composition relative to 100 mass % of the resin component of the resin composition can be 0 mass % or greater than 0 mass %, preferably 0.01 mass % or more, more preferably 0.1 mass % or more, further preferably 1 mass % or more, preferably 20 mass % or less, more preferably 15 mass % or less, further preferably 10 mass % or less.
[0098] The amount (mass %) of the curing accelerator (C) contained in the resin composition relative to 100 mass % of the thermosetting resin (B) may be 0 mass % or greater than 0 mass %, and is preferably 0.01 mass % or greater, more preferably 0.1 mass % or greater, further preferably 1 mass % or greater, and is preferably 20 mass % or less, more preferably 15 mass % or less, further preferably 10 mass % or less.
[0099] <(D) Thermoplastic resin> The resin composition according to the present embodiment may further include a (D) thermoplastic resin as an arbitrary component in combination with the above-mentioned (A) to (C) components. The (D) thermoplastic resin as the (D) component does not include the resins belonging to the above-mentioned (A) to (C) components. The (D) thermoplastic resin can effectively improve the mechanical properties of the magnetic layer.
[0100] (D) Thermoplastic resins include, for example, phenoxy resins, polyimide resins, polyvinyl acetal resins, polyolefin resins, polybutadiene resins, polyamide-imide resins, polyetherimide resins, polysulfone resins, polyethersulfone resins, polyphenylene ether resins, polycarbonate resins, polyetheretherketone, polyester resins, etc. (D) Thermoplastic resins may be used alone or in combination of two or more.
[0101] Examples of the phenoxy resin include phenoxy resins having one or more skeletons selected from the group consisting of a bisphenol A skeleton, a bisphenol F skeleton, a bisphenol S skeleton, a bisphenol acetophenone skeleton, a phenolic skeleton, a biphenyl skeleton, a fluorene skeleton, a dicyclopentadiene skeleton, a norbornene skeleton, a naphthalene skeleton, an anthracene skeleton, an adamantane skeleton, a terpene skeleton, and a trimethylcyclohexane skeleton. Specific examples of phenoxy resins include "1256" and "4250" manufactured by Mitsubishi Chemical Corporation (both are phenoxy resins containing a bisphenol A skeleton); "YX8100" manufactured by Mitsubishi Chemical Corporation (a phenoxy resin containing a bisphenol S skeleton); "YX6954" manufactured by Mitsubishi Chemical Corporation (a phenoxy resin containing a bisphenol acetophenone skeleton); "FX280" and "FX293" manufactured by Nippon Steel & Sumitomo Metal Chemicals; "YL7500BH30", "YX6954BH30", "YX7553", "YX7553BH30", "YL7769BH30", "YL6794", "YL7213", "YL7290", "YL7482" and "YL7891BH30" manufactured by Mitsubishi Chemical Corporation.
[0102] Specific examples of polyimide resins include "SLK-6100" manufactured by Shin-Etsu Chemical Co., Ltd., "RIKACOAT SN20" and "RIKACOAT PN20" manufactured by Shin-Nippon Chemical Co., Ltd. Specific examples of polyimide resins include linear polyimides obtained by reacting difunctional hydroxy-terminated polybutadiene, a diisocyanate compound and a tetrabasic acid anhydride (for example, polyimides described in Japanese Patent Laid-Open No. 2006-37083), polyimides containing a polysiloxane skeleton (for example, polyimides described in Japanese Patent Laid-Open No. 2002-12667 and Japanese Patent Laid-Open No. 2000-319386, etc.), and the like.
[0103] Examples of the polyvinyl acetal resin include polyvinyl formal resin and polyvinyl butyral resin, and polyvinyl butyral resin is preferred. Specific examples of the polyvinyl acetal resin include "Denka Butyral 4000-2", "Denka Butyral 5000-A", "Denka Butyral 6000-C", and "Denka Butyral 6000-EP" manufactured by Denki Kagaku Kogyo Co., Ltd.; and S-LEC BH series, BX series (e.g., BX-5Z), KS series (e.g., KS-1), BL series, and BM series manufactured by Sekisui Chemical Co., Ltd.
[0104] Examples of the polyolefin resin include ethylene copolymer resins such as low-density polyethylene, ultra-low-density polyethylene, high-density polyethylene, ethylene-vinyl acetate copolymers, ethylene-ethyl acrylate copolymers, and ethylene-methyl acrylate copolymers; and polyolefin polymers such as polypropylene and ethylene-propylene block copolymers.
[0105] Examples of the polybutadiene resin include resins containing a hydrogenated polybutadiene skeleton, hydroxyl-containing polybutadiene resins, phenolic hydroxyl-containing polybutadiene resins, carboxyl-containing polybutadiene resins, acid anhydride-containing polybutadiene resins, epoxy-containing polybutadiene resins, isocyanate-containing polybutadiene resins, urethane-containing polybutadiene resins, and polyphenylene ether-polybutadiene resins.
[0106] Specific examples of polyamideimide resins include "VYLOMAX HR11NN" and "VYLOMAX HR16NN" manufactured by Toyobo Co., Ltd. Specific examples of polyamideimide resins include modified polyamideimides such as "KS9100" and "KS9300" (polyamideimide containing a polysiloxane skeleton) manufactured by Hitachi Chemical Co., Ltd.
[0107] Specific examples of the polyetherimide resin include "Ultem" manufactured by GE.
[0108] Specific examples of the polysulfone resin include polysulfone "P1700" and "P3500" manufactured by Solvay Performance Polymers.
[0109] Specific examples of the polyethersulfone resin include "PES5003P" manufactured by Sumitomo Chemical Co., Ltd. and the like.
[0110] Specific examples of the polyphenylene ether resin include "NORYL SA90" manufactured by SABIC.
[0111] As polycarbonate resin, for example, carbonate resin containing hydroxyl group, carbonate resin containing phenolic hydroxyl group, carbonate resin containing carboxyl group, carbonate resin containing acid anhydride group, carbonate resin containing isocyanate group, carbonate resin containing urethane group, etc. As specific examples of polycarbonate resin, "FPC0220" manufactured by Mitsubishi Gas Chemical Co., Ltd., "T6002", "T6001" (polycarbonate diol) manufactured by Asahi Kasei Chemicals Co., Ltd., "C-1090", "C-2090", "C-3090" (polycarbonate diol) manufactured by Kuraray Co., Ltd., etc. can be mentioned.
[0112] Specific examples of the polyetheretherketone resin include "Sumiploy K" manufactured by Sumitomo Chemical Co., Ltd. and the like.
[0113] Examples of the polyester resin include polyethylene terephthalate resin, polyethylene naphthalate resin, polybutylene terephthalate resin, polybutylene naphthalate resin, polytrimethylene terephthalate resin, polytrimethylene naphthalate resin, and polycyclohexylene dimethyl terephthalate resin.
[0114] The weight average molecular weight (Mw) of the (D) thermoplastic resin is preferably greater than 5000, more preferably 8000 or more, further preferably 10000 or more, and further preferably 20000 or more. The upper limit is not particularly limited, and may be, for example, 1 million or less, 500,000 or less, or 100,000 or less.
[0115] The amount (mass %) of the (D) thermoplastic resin contained in the resin composition relative to 100 mass % of the non-volatile components of the resin composition may be 0 mass % or greater than 0 mass %, and is preferably 0.01 mass % or greater, more preferably 0.05 mass % or greater, further preferably 0.1 mass % or greater, and is preferably 5 mass % or less, more preferably 3 mass % or less, and further preferably 1 mass % or less.
[0116] The amount (mass %) of the (D) thermoplastic resin contained in the resin composition relative to 100 mass % of the resin component of the resin composition may be 0 mass % or greater than 0 mass %, and is preferably 1 mass % or greater, more preferably 5 mass % or greater, further preferably 10 mass % or greater, and is preferably 30 mass % or less, more preferably 20 mass % or less, and further preferably 15 mass % or less.
[0117] The amount (mass %) of the (D) thermoplastic resin contained in the resin composition relative to 100 mass % of the (A) magnetic powder can be 0 mass % or greater than 0 mass %, and is preferably 0.01 mass % or more, more preferably 0.05 mass % or more, further preferably 0.1 mass % or more, preferably 5 mass % or less, more preferably 3 mass % or less, and further preferably 1 mass % or less.
[0118] <(E) Dispersant> The resin composition according to the present embodiment may further include a dispersant (E) as an arbitrary component in combination with the components (A) to (D). The dispersant (E) as the component (E) does not include any substance belonging to the components (A) to (D). The dispersant (E) can effectively improve the dispersibility of the magnetic powder (A).
[0119] As the (E) dispersant, a compound that can reduce the viscosity of the resin composition can be used. As the (E) dispersant, for example, a phosphate dispersant, a polyoxyalkylene dispersant, an acetylene dispersant, a silicone dispersant, an anionic dispersant, a cationic dispersant, etc. can be mentioned. The (E) dispersant can be used alone or in combination of two or more. Among them, a phosphate dispersant is preferred.
[0120] Among the phosphate ester dispersants, polyether phosphate ester dispersants are preferred. Polyether phosphate ester dispersants are phosphate ester dispersants containing a poly(alkylene oxide) structure in the molecule. Examples of polyether phosphate ester dispersants include polyoxyalkylene alkyl ether phosphates and polyoxyalkylene alkylphenyl ether phosphates. Among them, polyoxyalkylene alkyl ether phosphates are preferred.
[0121] The polyoxyalkylene alkyl ether phosphate may have a structure in which 1 to 3 alkyl-oxy-poly(alkyleneoxy) groups are bonded to the phosphorus atom of the phosphate. The number of alkyleneoxy units (number of repeating units) in the poly(alkyleneoxy) moiety in the alkyl-oxy-poly(alkyleneoxy) moiety is preferably 2 to 30, and more preferably 3 to 20. In addition, the alkylene group in the poly(alkyleneoxy) moiety is preferably an alkylene group having 2 to 4 carbon atoms. Examples of such alkylene groups include ethylene, propylene, isopropylene, butylene, and isobutylene. Furthermore, the alkyl group in the alkyl-oxy-poly(alkyleneoxy) moiety is preferably an alkyl group having 6 to 30 carbon atoms, and more preferably an alkyl group having 8 to 20 carbon atoms. Examples of such alkyl groups include decyl, undecyl, dodecyl, tridecyl, tetradecyl, pentadecyl, hexadecyl, heptadecyl, and octadecyl. In addition, when the polyoxyalkylene alkyl ether phosphate has a plurality of alkyl-oxy-poly(alkyleneoxy) groups, the plurality of alkyl groups may be the same or different. Furthermore, the plurality of alkylene groups may be the same or different.
[0122] Examples of commercially available phosphate ester dispersants include polyether phosphate ester dispersants manufactured by Kusumoto Chemicals Co., Ltd. (e.g., HIPLAAD series "ED152", "ED153", "ED154", "ED118", "ED174", "ED251", etc.); and "Phosphanol" series "RS-410", "RS-610", "RS-710", etc. manufactured by Toho Chemical Industries, Ltd.
[0123] Examples of the polyoxyalkylene dispersant include polyoxyethylene alkyl ethers, polyoxyethylene alkyl esters, polyoxyethylene sorbitan fatty acid esters, polyoxyethylene alkylphenyl ethers, polyoxyethylene alkylamines, polyoxyethylene alkylamides, etc. Examples of commercially available polyoxyalkylene dispersants include "AKM-0531", "AFB-1521", "SC-0505K", "SC-1015F", "SC-0708A", and "HKM-50A" of the "Malialim" series manufactured by NOF Corporation.
[0124] Examples of acetylene dispersants include acetylene glycol, and examples of commercially available acetylene dispersants include "82", "104", "440", "465", "485" and "Olefin Y" of the "SURFYNOL" series manufactured by Air Products and Chemicals Inc.
[0125] Examples of the silicone dispersant include polyether-modified polydimethylsiloxane, polyether-modified siloxane, polyester-modified polydimethylsiloxane, etc. Examples of commercially available silicone dispersants include BYK-Chemie's "BYK347" and "BYK348".
[0126] Examples of the anionic dispersant include sodium polyacrylate, sodium dodecylbenzenesulfonate, sodium laurate, ammonium polyoxyethylene alkyl ether sulfate, sodium carboxymethyl cellulose, etc. Examples of commercially available anionic dispersants include "PN-411" and "PA-111" manufactured by Ajinomoto Fine Technologies Co., Ltd.; and "A-550" and "PS-1900" manufactured by Lion Corporation.
[0127] Examples of cationic dispersants include polyacrylate resins containing amino groups, polystyrene resins containing amino groups, etc. Examples of commercially available cationic dispersants include "161", "162", "164", "182", "2000", and "2001" manufactured by BYK Chemicals; "PB-821", "PB-822", and "PB-824" manufactured by Ajinomoto Fine Technologies; "V-216" and "V-220" manufactured by ISP Japan; and "Solsperse 13940", "Solsperse 24000", and "Solsperse 32000" manufactured by Lubrizol.
[0128] (E) The dispersant may be used alone or in combination of two or more.
[0129] The amount (mass %) of the (E) dispersant contained in the resin composition relative to 100 mass % of the non-volatile component of the resin composition may be 0 mass % or greater than 0 mass %, and is preferably 0.01 mass % or greater, more preferably 0.05 mass % or greater, further preferably 0.1 mass % or greater, and is preferably 5 mass % or less, more preferably 3 mass % or less, further preferably 1 mass % or less.
[0130] The amount (mass %) of the (E) dispersant contained in the resin composition relative to 100 mass % of the resin component of the resin composition may be 0 mass % or greater than 0 mass %, and is preferably 0.1 mass % or greater, more preferably 1 mass % or greater, further preferably 5 mass % or greater, and is preferably 30 mass % or less, more preferably 20 mass % or less, and further preferably 15 mass % or less.
[0131] The amount (mass %) of the (E) dispersant contained in the resin composition relative to 100 mass % of the (A) magnetic powder can be 0 mass % or greater than 0 mass %, and is preferably 0.01 mass % or more, more preferably 0.05 mass % or more, further preferably 0.1 mass % or more, preferably 5 mass % or less, more preferably 3 mass % or less, and further preferably 1 mass % or less.
[0132] <(F) Optional Additives> The resin composition according to the present embodiment may further include (F) an optional additive as an optional component in combination with the above-mentioned components (A) to (E). The (F) optional additive as the component (F) does not include any of the above-mentioned components (A) to (E).
[0133] Examples of the optional additive (F) include inorganic fillers such as silica particles; organic fillers such as rubber particles; organic metal compounds such as organic copper compounds and organic zinc compounds; free radical polymerization initiators such as peroxide-based free radical polymerization initiators and azo-based free radical polymerization initiators; polymerization inhibitors such as hydroquinone, catechol, pyrogallol, and phenothiazine; leveling agents such as silicone-based leveling agents and acrylic polymer-based leveling agents; thickeners such as bentonite and montmorillonite; defoamers such as silicone-based defoamers, acrylic defoamers, fluorine-based defoamers, and vinyl resin-based defoamers; benzotriazole-based ultraviolet light absorbers, etc. Ultraviolet absorbers; adhesion enhancers such as urea silane; adhesion imparting agents such as triazole-based adhesion imparting agents, tetrazole-based adhesion imparting agents, and triazine-based adhesion imparting agents; antioxidants such as hindered phenol-based antioxidants; flame retardants such as phosphorus-based flame retardants (such as phosphate compounds, phosphazene compounds, phosphinic acid compounds, and red phosphorus), nitrogen-based flame retardants (such as melamine sulfate), halogen-based flame retardants, and inorganic flame retardants (such as antimony trioxide); stabilizers such as borate-based stabilizers, titanate-based stabilizers, aluminate-based stabilizers, zirconate-based stabilizers, isocyanate-based stabilizers, carboxylic acid-based stabilizers, and carboxylic anhydride-based stabilizers, etc. (F) Any additive may be used alone or in combination of two or more.
[0134] <(G)Solvent> The resin composition may also be combined with non-volatile components such as the above-mentioned (A) to (F) components to further contain (G) a solvent as a volatile component. As the (G) solvent, an organic solvent is generally used. Examples of the organic solvent include ketone solvents such as acetone, methyl ethyl ketone (MEK), methyl isobutyl ketone, and cyclohexanone; ester solvents such as methyl acetate, ethyl acetate, butyl acetate, isobutyl acetate, isoamyl acetate, methyl propionate, ethyl propionate, and γ-butyrolactone; ether solvents such as tetrahydropyran, tetrahydrofuran, 1,4-dioxane, diethyl ether, diisopropyl ether, dibutyl ether, and diphenyl ether; alcohol solvents such as methanol, ethanol, propanol, butanol, and ethylene glycol; 2-ethoxyethyl acetate, propylene glycol monomethyl ether acetate, diethylene glycol monoethyl ether acetate, butyl carbitol acetate, and carbitol acetate (ethyl diglycol Ether ester solvents such as acetate, γ-butyrolactone, and methyl methoxypropionate; ester alcohol solvents such as methyl lactate, ethyl lactate, and methyl 2-hydroxyisobutyrate; ether alcohol solvents such as 2-methoxypropanol, 2-methoxyethanol, 2-ethoxyethanol, propylene glycol monomethyl ether, and diethylene glycol monobutyl ether (butyl carbitol); amide solvents such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methyl-2-pyrrolidone; sulfoxide solvents such as dimethyl sulfoxide; nitrile solvents such as acetonitrile and propionitrile; aliphatic hydrocarbon solvents such as hexane, cyclopentane, cyclohexane, and methylcyclohexane; aromatic hydrocarbon solvents such as benzene, toluene, xylene, ethylbenzene, and trimethylbenzene. (G) Solvents can be used alone or in combination of two or more.
[0135] <Method for producing resin composition> The resin combination involved in the present embodiment can be manufactured by mixing the above-mentioned components, for example. The above-mentioned components can be mixed in part or in whole at the same time, or can be mixed successively. In the process of mixing each component, the temperature can be appropriately set, so heating and / or cooling can be performed temporarily or all the time. In addition, in the process of mixing each component, stirring or vibration can also be performed.
[0136] <Characteristics of Resin Composition> The resin composition involved in the present embodiment can be cured by heat. Therefore, by thermally curing the resin composition, a cured product of the resin composition can be obtained. Usually, among the components contained in the resin composition, volatile components such as (G) solvents can be volatilized due to the heat during thermal curing, while non-volatile components such as (A) to (F) components will not be volatilized due to the heat during thermal curing. Therefore, the cured product of the resin composition can contain the non-volatile components of the resin composition or their reaction products. The cured product of the resin composition can have excellent magnetic properties such as relative permeability and magnetic loss. Therefore, the cured product can be used as a material for the magnetic layer of a magnetic substrate.
[0137] The cured product of the resin composition involved in the present embodiment can generally have a high relative magnetic permeability μ'. The specific relative magnetic permeability μ' of the cured product is preferably in the range of 10 or more, more preferably in the range of 12 or more, and further preferably in the range of 15 or more. The upper limit of the relative magnetic permeability μ' is not particularly limited, and can be, for example, 35 or less, 30 or less, 25 or less, etc. In the method for manufacturing a magnetic substrate involved in the present embodiment, when using a resin composition containing an amount of (A) magnetic powder that can achieve such a relative magnetic permeability, a plating layer can be smoothly formed on the surface of a magnetic layer of a cured product containing the resin composition by electroplating. The relative magnetic permeability μ' of the cured product can be measured under the conditions of a measuring frequency of 20 MHz and a room temperature of 23°C. In addition, when the resin composition is cured in order to measure the relative magnetic permeability μ', the resin composition can be thermally cured at 190°C for 90 minutes to obtain a cured product as a measurement sample. The specific method for measuring the relative magnetic permeability μ' can adopt the method described in the embodiments described later.
[0138] The cured product of the resin composition involved in the present embodiment can generally have a small magnetic loss. The magnetic loss can be represented by the loss coefficient tanδ, and generally the smaller the loss coefficient tanδ is, the smaller the magnetic loss is. The specific loss coefficient tanδ of the cured product is preferably in the range of 0.05 or less, more preferably in the range of 0.04 or less, and further preferably in the range of 0.03 or less. The lower limit of the loss coefficient tanδ is not particularly limited, and for example, it can be 0.001 or more. The method for manufacturing a magnetic substrate involved in the present embodiment, when using a resin composition containing an amount of (A) magnetic powder that can achieve such a range of magnetic loss, can smoothly form an electroplating layer on the surface of a magnetic layer of a cured product containing the resin composition by electroplating. The loss coefficient tanδ of the cured product can be measured under the conditions of a measurement frequency of 20 MHz and a room temperature of 23°C. In addition, when the resin composition is cured in order to measure the loss coefficient tanδ, the resin composition can be thermally cured at 190°C and 90 minutes to obtain a cured product as a measurement sample. The specific method for measuring the loss coefficient tanδ can adopt the method described in the embodiments described later.
[0139] The cured product of the resin composition according to the present embodiment can generally have a large volume resistivity. Therefore, a magnetic layer having insulating properties can be formed according to the cured product. The specific volume resistivity of the cured product is preferably in the range of 1.0×10 8 Ω·m or more, more preferably 5.0×10 8 Ω·m or more, more preferably 1.0×10 9 Ω·m or more, preferably 1.0×10 13 Ω·m or less, more preferably 5.0×10 12Ω·m or less, more preferably 1.0×10 12 Ω·m or less. From the technical common sense of those skilled in the art, it is unexpected that a plated layer can be formed by electroplating on the surface of a magnetic layer formed of a solidified material having such a large volume resistance. The volume resistance of the solidified material can be determined by the method described in the examples described later.
[0140] The properties of the resin composition are not particularly limited. Therefore, the resin composition may be a liquid having fluidity. For example, the resin composition may be a liquid resin composition not containing the (G) solvent, or a liquid resin composition containing the (G) solvent. Hereinafter, a liquid resin composition not containing the (G) solvent may be referred to as a "magnetic paste", and a liquid resin composition containing the (G) solvent may be referred to as a "magnetic ink".
[0141] Liquid resin compositions such as magnetic pastes and magnetic inks have fluidity and can therefore be preferably used for the formation of a magnetic layer using a printing method. The liquid resin composition is preferably liquid at 23°C. The viscosity of the liquid resin composition is preferably 20 Pa·s or more at 23°C, more preferably 25 Pa·s or more, further preferably 30 Pa·s or more, particularly preferably 50 Pa·s or more, preferably 200 Pa·s or less, more preferably 180 Pa·s or less, and further preferably 160 Pa·s or less. The viscosity can be measured, for example, using an E-type viscometer ("RE-80U", 3°×R9.7 rotor manufactured by Toki Sangyo Co., Ltd.) under the conditions of a sample volume of 0.22 ml and a rotation speed of 5 rpm.
[0142] The resin composition may also be in a solid state. The form of the solid resin composition is not particularly limited, and may be, for example, in the form of particles, flakes, or films. Among them, since a magnetic layer can be formed by lamination, a film is preferred. The film-like resin composition is usually prepared as a resin sheet having a resin composition layer as a film of the resin composition.
[0143] The resin composition layer contains a resin composition, preferably only a resin composition. The thickness of the resin composition layer can be set according to the size of the magnetic substrate to be manufactured. Generally, the resin composition layer is preferably thinner. The specific thickness range of the resin composition layer is preferably 5 μm or more, more preferably 10 μm or more, more preferably 50 μm or more, preferably 600 μm or less, more preferably 300 μm or less, more preferably 200 μm or less, and more preferably 150 μm or less.
[0144] The resin sheet may be combined with the resin composition layer to further include any member. For example, the resin sheet may include a support that supports the resin composition layer. In a resin sheet including a support, the resin composition layer is usually formed on the support.
[0145] Examples of the support include films of plastic materials, metal foils, and release papers, and films and metal foils formed of plastic materials are preferred.
[0146] When a film of a plastic material is used as a support, the plastic material includes polyesters such as polyethylene terephthalate (hereinafter sometimes referred to as "PET") and polyethylene naphthalate (hereinafter sometimes referred to as "PEN"), polycarbonate (hereinafter sometimes referred to as "PC"), acrylic polymers such as polymethyl methacrylate (PMMA), cyclic polyolefins, triacetyl cellulose (TAC), polyether sulfide (PES), polyether ketone, polyimide, etc. Among them, polyethylene terephthalate and polyethylene naphthalate are preferred, and inexpensive polyethylene terephthalate is particularly preferred.
[0147] When a metal foil is used as a support, examples of the metal foil include copper foil and aluminum foil. Copper foil is preferred. As the copper foil, a foil formed of a single metal of copper can be used, or a foil formed of an alloy of copper and other metals (such as tin, chromium, silver, magnesium, nickel, zirconium, silicon, titanium, etc.) can be used.
[0148] The support may be subjected to a matte treatment, a corona treatment, an antistatic treatment, or the like on the surface to be bonded to the resin composition layer.
[0149] As the support, a support with a release layer having a release layer on the surface bonded to the resin composition layer can be used. As the release agent used in the release layer of the support with a release layer, for example, one or more release agents selected from alkyd release agents, polyolefin release agents, polyurethane release agents, and silicone release agents can be cited. The support with a release layer can also use commercial products, for example, it can be a PET film having a release layer with a silicone release agent or an alkyd resin release agent as the main component, that is, "PET501010", "SK-1", "AL-5", "AL-7" manufactured by Lintec; "Lumirror T60" manufactured by Toray Industries; "Purex" manufactured by Teijin; "Unipeel" manufactured by Unitika, etc.
[0150] The thickness of the support is not particularly limited, but is preferably 1 μm or more, more preferably 5 μm or more, further preferably 10 μm or more, preferably 75 μm or less, more preferably 60 μm or less, further preferably 50 μm or less. When a support with a release layer is used, the overall thickness of the support with the release layer is preferably within the above range.
[0151] As required, the resin sheet may be provided with a protective film for protecting the resin composition layer. The protective film is usually provided on the surface of the resin composition layer that is not bonded to the support (i.e., the surface on the opposite side of the support). The thickness of the protective film is not particularly limited, for example, 1 μm to 40 μm. When there is a protective film, it is possible to suppress the attachment of garbage and damage to the surface of the resin composition layer. When using a resin sheet with a protective film, the protective film is usually peeled off before step (LF).
[0152] The resin sheet can be manufactured, for example, by a method comprising forming a resin composition layer on a support. The resin composition layer can be formed, for example, by a method comprising preparing a resin composition and coating the resin composition on a support. As required, an organic solvent can be mixed in the resin composition and then coated on a support. When an organic solvent is used, it can also be dried after coating as required.
[0153] The coating of the resin composition can be carried out using a coating device such as a die coater. In addition, drying can be carried out, for example, by a drying method such as heating or hot air blowing. The drying conditions are not particularly limited, and the amount of the solvent in the resin composition layer is preferably 10% by mass or less, more preferably 5% by mass or less. The drying conditions also vary depending on the boiling point of the solvent, and for example, drying can be carried out at 50° C. to 150° C. for 3 minutes to 10 minutes.
[0154] [Step (LF): Formation of Resin Composition Layer] The method for producing a magnetic substrate according to the present embodiment may include a step (LF) of forming a resin composition layer before step (EP). In step (LF), a resin composition layer is usually formed on a suitable substrate. Hereinafter, the substrate may be referred to as an "inner layer substrate".
[0155] As the inner layer substrate, for example, a component including a supporting substrate can be used. As the supporting substrate, insulating substrates such as glass epoxy substrates, metal substrates, polyester substrates, polyimide substrates, BT resin substrates, and thermosetting polyphenylene ether substrates can be cited. In addition, as needed, the inner layer substrate can also be provided with conductor layers such as wiring layers and electrode layers. In the following description, the conductor layer possessed by the inner layer substrate is sometimes referred to as a "substrate conductor layer". The substrate conductor layer can be provided on a single surface of the supporting substrate, can be provided on both surfaces, or can be provided inside. As the substrate conductor layer, a layer formed by metals such as copper can be cited. In addition, holes such as through holes can also be formed in the inner layer substrate as needed. The hole formed in the inner layer substrate is sometimes referred to as a "first hole" hereinafter. The first hole can be formed, for example, by processing methods such as drilling, laser irradiation, and plasma irradiation. As needed, a substrate conductor layer can be formed on the surface of the inner layer substrate in the first hole.
[0156] The method for forming a resin composition layer on an inner substrate is not limited. For example, in the case of using a liquid resin composition, a resin composition layer can be formed by applying a resin composition on an inner substrate. As a specific example, a coating device such as a dispenser, a die coater, etc. can be used to apply the resin composition to the inner substrate to form a resin composition layer. In addition, the resin composition layer can be applied to the inner substrate by printing such as full-face printing or pattern printing to form a resin composition layer. As a printing method, for example, a method for printing a resin composition via a scraper (squeegee), a method for printing a resin composition via a cartridge (cartridge), a method for printing a resin composition by mask printing, a roller coating method, an inkjet method, etc. can be cited. And then, as required, it can be dried after the coating of the resin composition.
[0157] For example, in the case of using a resin sheet with a resin composition layer, the resin sheet and the inner layer substrate can be stacked in a manner that the resin composition layer is bonded to the inner layer substrate, and a resin composition layer is formed on the inner layer substrate. The bonding of the resin composition layer and the inner layer substrate can be carried out, for example, by heat-pressing the resin sheet to the inner layer substrate from the support body side. As a component (hereinafter also referred to as "heat-pressing component") for heat-pressing the resin sheet to the inner layer substrate, for example, a heated metal plate (stainless steel (SUS) end plate, etc.) or a metal roller (SUS roller, etc.) can be cited. It should be noted that it is preferred that the heat-pressing component is not pressed in direct contact with the resin sheet, but is pressed via a sheet formed of an elastic material such as a heat-resistant rubber, so that the resin sheet fully follows the surface concave-convex of the inner layer substrate.
[0158] The temperature during heat pressing is preferably 80°C to 160°C, more preferably 90°C to 140°C, and further preferably in the range of 100°C to 120°C. The pressure during heat pressing is preferably 0.098MPa to 1.77MPa, and more preferably in the range of 0.29MPa to 1.47MPa. The time during heat pressing is preferably 20 seconds to 400 seconds, and more preferably in the range of 30 seconds to 300 seconds. The bonding of the resin sheet and the inner layer substrate is preferably carried out under reduced pressure conditions of 26.7hPa or less.
[0159] The resin composition layer of the resin sheet and the inner layer substrate can be bonded together using a commercially available vacuum laminator, such as a vacuum pressure laminator manufactured by Meiki Seisakusho Co., Ltd. and a vacuum laminator manufactured by Nikko-Materials Co., Ltd.
[0160] After the resin sheet is joined to the inner layer substrate, the laminated resin sheet can be smoothed by, for example, pressing the heating and pressing member from the support body side under normal pressure (atmospheric pressure). The pressing conditions for the smoothing treatment can be the same as the heating and pressing conditions for the above-mentioned lamination. The smoothing treatment can be performed using a commercially available laminator. It should be noted that the lamination and smoothing treatment can also be performed continuously using the above-mentioned commercially available vacuum laminator.
[0161] When a resin sheet having a support is used, the support is usually peeled off after step (LF). Peeling of the support may be performed before step (CU) or after step (CU), but is preferably performed before step (EP).
[0162] In the case where the inner layer substrate is formed with a first hole, step (LF) may include forming a resin composition layer in the first hole. Typically, the resin composition is filled in the first hole to form a resin composition layer. For example, a liquid resin composition may be applied to the inner layer substrate formed with the first hole, thereby filling the resin composition in the first hole, and forming a resin composition layer in the first hole. In addition, for example, the inner layer substrate formed with the first hole may be stacked with a resin sheet, thereby filling the resin composition in the first hole, and forming a resin composition layer in the first hole.
[0163] [Step (CU): Curing of Resin Composition Layer] The method for manufacturing a magnetic substrate according to the present embodiment may include a step (CU) of curing the resin composition layer to form a magnetic layer after the step (LF). Typically, the resin composition layer is thermally cured under specific thermal curing conditions to obtain a magnetic layer. The magnetic layer includes a cured product of the resin composition, preferably only includes a cured product of the resin composition.
[0164] The heat curing conditions of the resin composition layer can be appropriately set within the range of curing of the resin composition. The curing temperature is preferably 120°C or more, more preferably 130°C or more, more preferably 150°C or more, preferably 245°C or less, more preferably 220°C or less, and more preferably 200°C or less. The curing time is preferably 5 minutes or more, more preferably 10 minutes or more, more preferably 15 minutes or more, preferably 120 minutes or less, more preferably 110 minutes or less, and more preferably 100 minutes or less.
[0165] The method for producing a magnetic substrate according to the present embodiment may include a step (preheating step) of heating the resin composition layer at a temperature lower than the above-mentioned curing temperature after forming the resin composition layer and before curing the resin composition layer. For example, before curing the resin composition layer, the resin composition layer may be preheated at a temperature of 50°C or more and less than 150°C (preferably 60°C or more and 140°C or less, more preferably 70°C or more and 130°C or less) for usually 5 minutes or more (preferably 5 minutes to 150 minutes, more preferably 15 minutes to 120 minutes).
[0166] [Process (PO): Grinding] The manufacturing method of the magnetic substrate involved in the present embodiment may include a step (PO) of grinding the resin composition layer or the magnetic layer before the step (EP). By grinding, the surface of the magnetic layer can be smoothed. For example, in the case of grinding the magnetic layer, the surface of the ground magnetic layer can be flattened. In addition, in the case of grinding the resin composition layer, since the surface of the resin composition layer can be flattened, the surface of the magnetic layer obtained by curing the resin composition layer can be flattened. In particular, in the case where the first hole of the inner substrate is filled with a resin composition to form a resin composition layer, the remaining resin composition protrudes from the first hole or adheres to the part of the inner substrate outside the first hole, and can form a concave-convex on the surface of the resin composition layer. Therefore, from the viewpoint of improving the flatness of the surface of the magnetic layer by grinding to remove the above-mentioned concave-convex, the step (PO) is preferably implemented when using an inner substrate with a first hole.
[0167] Examples of the polishing method include buffing, belt polishing, and ceramic polishing. Examples of commercially available buffing devices include "NT-700IM" manufactured by Ishii Hyoki Co., Ltd.
[0168] The arithmetic mean roughness (Ra) of the ground surface (after the thermal curing of the solidified material layer) of the magnetic layer is preferably 300 nm or more, more preferably 350 nm or more, and further preferably 400 nm or more from the viewpoint of improving the adhesion between the electroplated layer. The upper limit is preferably 1000 nm or less, more preferably 900 nm or less, and further preferably 800 nm or less. The surface roughness (Ra) can be measured, for example, using a non-contact surface roughness meter.
[0169] In the case where the magnetic layer is obtained by curing the resin composition layer and then grinding, the magnetic layer may be subjected to heat treatment before grinding for the purpose of further increasing the degree of curing of the cured product contained in the magnetic layer. The temperature in the heat treatment may be based on the above-mentioned curing temperature. The specific heat treatment temperature is preferably above 120°C, more preferably above 130°C, more preferably above 150°C, preferably below 245°C, more preferably below 220°C, and more preferably below 200°C. The heat treatment time is preferably above 5 minutes, more preferably above 10 minutes, more preferably above 15 minutes, preferably below 90 minutes, more preferably below 70 minutes, and more preferably below 60 minutes.
[0170] On the other hand, when grinding is performed before the resin composition layer is cured to obtain the magnetic layer, a preheating treatment of heating the resin composition layer at a temperature lower than the curing temperature of the resin composition may be performed before grinding. The temperature in the preheating treatment is preferably 100°C or higher, more preferably 110°C or higher, further preferably 120°C or higher, preferably 245°C or lower, more preferably 220°C or lower, further preferably 200°C or lower. The heat treatment time is preferably 5 minutes or more, more preferably 10 minutes or more, further preferably 15 minutes or more, preferably 90 minutes or less, more preferably 70 minutes or less, further preferably 60 minutes or less.
[0171] [Step (HF): Formation of Second Hole] The method for manufacturing a magnetic substrate according to the present embodiment may include a step (HF) of forming a hole in the magnetic layer before the step (EP). The hole formed in the magnetic layer is sometimes referred to as a "second hole" below. Usually, the second hole is formed after the step (CU). In addition, the second hole may be formed before the grinding in the step (PO), but is usually performed after the grinding in the step (PO).
[0172] As the second hole, a via hole, a through hole, etc. can be cited. For example, in the case where the second hole is formed on the magnetic layer of the first hole formed in the inner substrate, the second hole can also be a through hole that penetrates the magnetic layer. In addition, for example, in the case where the second hole is formed on the magnetic layer formed on the main surface of the inner substrate, the second hole can be a via hole that penetrates the magnetic layer but does not penetrate the inner substrate, or a through hole that penetrates both the magnetic layer and the inner substrate. The second hole can be formed, for example, by drilling, laser processing, plasma irradiation, etching, and other processing methods.
[0173] [Process (RO): Roughening] The method for manufacturing a magnetic substrate according to the present embodiment may include a step (RO) of roughening the magnetic layer before the step (EP). Usually, the roughening treatment is performed after the step (PO). In addition, usually, the roughening treatment is performed after the step (HF). According to the roughening treatment, the surface roughness of the magnetic layer can be increased, and the adhesion strength between the magnetic layer and the electroplating layer can be improved. In addition, according to the roughening treatment, the resin residue (contamination) that may be generated due to the formation of the second hole can be removed. The roughening treatment can be performed in a wet manner, but is preferably performed in a dry manner. As a dry roughening treatment, plasma treatment and the like can be cited.
[0174] [Process (EP): Electroplating] The manufacturing method of the magnetic substrate involved in the present embodiment includes a step (EP) of forming an electroplated layer as a conductor layer on the surface of the magnetic layer by electroplating. In electroplating, the electroplated layer is usually formed on the surface of the magnetic layer in a plating solution as a solution containing metal ions. For example, a magnetic layer and an electrode are placed in the plating solution, and a direct current is applied between the magnetic layer and the electrode from a power supply. Since the metal ions are reduced on the surface of the magnetic layer and the metal is precipitated, an electroplated layer containing the metal can be formed. As the metal used for electroplating, copper is preferred.
[0175] Usually, as the plating solution, an aqueous solution of a metal salt is used. As the metal salt, there is no restriction as long as it can form an electroplated layer. For example, when copper is used as the metal, as the copper salt, copper halides such as copper sulfate, copper chloride, copper acetate, copper nitrate, copper tetrafluoroborate, alkyl copper sulfonate, aryl copper sulfonate, copper sulfamate, copper perchlorate, copper gluconate, etc. can be cited. Among them, copper sulfate is preferred. The concentration of the metal salt in the plating solution can be, for example, more than 50g / L and less than 400g / L. The concentration of the metal salt in the plating solution is more preferably a saturated concentration.
[0176] The plating solution preferably contains an acid. Examples of the acid include sulfuric acid, hydrochloric acid, acetic acid, nitric acid, phosphoric acid, fluoroboric acid, alkanesulfonic acids such as methanesulfonic acid, ethanesulfonic acid, propanesulfonic acid, and trifluoromethanesulfonic acid, arylsulfonic acids such as benzenesulfonic acid, p-toluenesulfonic acid, and aminosulfonic acid, hydrobromic acid, perchloric acid, chromic acid, and the like. Among them, sulfuric acid, methanesulfonic acid, ethanesulfonic acid, propanesulfonic acid, hydrochloric acid, and combinations thereof are preferred, and sulfuric acid is more preferred. The concentration of the acid in the plating solution may be, for example, greater than 1 mL / L and less than 400 mL / L. In the case of using sulfuric acid, the concentration of the sulfuric acid is preferably greater than 40 mL / L, and is also preferably less than 200 mL / L.
[0177] The plating solution may contain additives. As additives that the plating solution may contain, for example, a halide ion supplier, a brightener, a surfactant, etc. may be cited. As a halide ion supplier, for example, chlorinated compounds such as sodium chloride and potassium chloride may be cited. The concentration of the halide ion supplier in the plating solution may be, for example, 0.5 mg / L or more and 300 mg / L or less. As a brightener, for example, organic sulfur compounds such as bis(3-sulfopropyl) disulfide salts may be cited. The concentration of the brightener in the plating solution may be, for example, 0.1 ppm or more and 1000 ppm or less. In addition, as a surfactant, for example, anionic surfactants, cationic surfactants, nonionic surfactants, etc. may be cited. The concentration of the surfactant in the plating solution may be, for example, 1 mL / L or more and 60 mL / L or less.
[0178] The temperature of the plating solution is not limited within the range in which a plated layer can be formed, but is preferably 2°C or higher, more preferably 10°C or higher, further preferably 15°C or higher, and preferably 80°C or lower, more preferably 50°C or lower, further preferably 30°C or lower.
[0179] The current density of the current applied during electroplating is not limited within the range in which the electroplated layer can be formed, but is preferably 0.5 A / dm 2 More preferably 1.0A / dm 2 Above, preferably 8.0A / dm 2 Below, more preferably 7.0A / dm 2 the following.
[0180] The electroplating may be performed while the plating solution is allowed to flow. The flow rate of the plating solution may be, for example, 3 cm / sec or more and 200 cm / sec or less.
[0181] According to the above-mentioned electroplating, an electroplating layer can be directly formed on the surface of the magnetic layer. The state of forming the electroplating layer on the surface of the magnetic layer is "directly" means that there is no other layer between the magnetic layer and the electroplating layer, and the magnetic layer is in contact with the electroplating layer. An interface is formed between the magnetic layer and the electroplating layer in contact, but there is usually no plating catalyst on the interface. Assuming that a conductor layer is formed on the magnetic layer by electroless plating, a plating catalyst such as palladium, gold, silver, platinum, etc. remains between the magnetic layer and the conductor layer, so the electroplating layer can be distinguished from the conductor layer formed by electroless plating due to the plating catalyst.
[0182] According to the above-mentioned electroplating, it is not necessary to form a thin conductor layer (seed layer) based on electroless plating, and an electroplated layer can be formed. Therefore, electroless plating can be omitted, reducing the number of steps in the method for manufacturing a magnetic substrate. From the viewpoint of effectively utilizing this advantage, the method for manufacturing a magnetic substrate involved in the present embodiment preferably does not include a step of forming a conductor layer on the surface of the magnetic layer by a method other than electroplating between the step (CU) of curing the resin composition layer to form a magnetic layer and the step (EP) of forming an electroplated layer on the surface of the magnetic layer.
[0183] As described above, since electroless plating is not performed, a liquid for electroless plating is not required, and therefore, the composition management of the liquid is not required. Therefore, it is possible to shorten the time and simplify the work of manufacturing the magnetic substrate. In addition, there is a substance in the liquid that can dissolve or deteriorate the alloy, but in the manufacturing method without using a liquid, as the (A-1) alloy powder, a substance that can dissolve or deteriorate in the liquid can be used. Therefore, the selection range of the (A-1) alloy powder can be expanded, so it is possible to expect the diversification and heightening of the magnetic substrate.
[0184] In the case where the magnetic layer is formed with a second hole, the step of forming the electroplating layer (EP) may include forming the electroplating layer on the surface of the second hole of the magnetic layer by electroplating. From the viewpoint of promoting the formation of the electroplating layer in the second hole, it is preferred to perform the electroplating in a state where the plating solution is circulated so that the plating solution can easily enter the second hole. In addition, from the viewpoint of more effectively forming the electroplating layer in the second hole, a process of applying ultrasonic waves to the plating solution may be performed.
[0185] The method for manufacturing a magnetic substrate according to the present embodiment may include a step of annealing the magnetic layer and the electroplated layer after electroplating (annealing step). The range of the treatment temperature of the annealing treatment is preferably above 150°C, more preferably above 160°C, further preferably above 170°C, preferably below 260°C, more preferably below 250°C, and further preferably below 240°C. In addition, the range of the treatment time of the annealing treatment is preferably above 10 minutes, more preferably above 20 minutes, further preferably above 30 minutes, preferably below 10 hours, more preferably below 5 hours, and further preferably below 2 hours. The annealing treatment may be performed in an inert atmosphere such as a nitrogen atmosphere. According to the annealing treatment, the adhesion strength between the magnetic layer and the electroplated layer can be improved.
[0186] As described above, by forming the electroplating layer on the surface of the magnetic layer, a magnetic substrate including the magnetic layer and the electroplating layer formed on the surface of the magnetic layer can be obtained. For example, when the electroplating layer is formed in a spiral shape alone, or when the electroplating layer and an arbitrary conductor layer included in the magnetic substrate are formed in a spiral shape in combination, an inductor can be formed using the electroplating layer and the arbitrary conductor layer, and thus an inductor-embedded substrate including the inductor can be obtained as a magnetic substrate.
[0187] The thickness of the electroplating layer is not particularly limited, and an appropriate range can be selected according to the application. In one example, the thickness range of the electroplating layer is preferably 1 μm or more, more preferably 3 μm or more, further preferably 5 μm or more, preferably 70 μm or less, more preferably 60 μm or less, and further preferably 50 μm or less.
[0188] The formed electroplated layer preferably has a smaller surface roughness. The arithmetic mean roughness Ra of the surface of the electroplated layer is preferably below 2000nm, more preferably below 1000nm, and further preferably below 800nm. The lower limit is not particularly limited, and can be above 1nm, above 10nm, above 50nm, etc. The surface roughness of the electroplated layer can be measured using a non-contact surface roughness meter.
[0189] [Optional process] The method for producing a magnetic substrate according to the present embodiment may further include an arbitrary step in combination with the above-mentioned steps.
[0190] The method for manufacturing a magnetic substrate may include, for example, a step of forming an arbitrary conductor layer. As a specific example, if an arbitrary conductor layer other than a base conductor layer and an electroplating layer is to be provided on a magnetic substrate, the method for manufacturing a magnetic substrate may include a step of forming an arbitrary conductor layer. The method for forming an arbitrary conductor layer may include, for example, a plating method, a sputtering method, a vapor deposition method, etc. In addition, an arbitrary conductor layer may be processed into a desired wiring pattern by an appropriate method such as a semi-additive method or a full-additive method.
[0191] Here, an example of a method for forming an arbitrary conductor layer is described in detail. A thin conductor layer (seed layer) is formed by electroless plating. Then, a conductor layer is further formed on the formed seed layer by electroplating. Then, as required, the unnecessary seed layer is removed by etching or the like, and an arbitrary conductor layer with a desired wiring pattern can be formed. After forming an arbitrary conductor layer, in order to improve the adhesion strength, an annealing treatment can be performed as required.
[0192] The method for manufacturing a magnetic substrate may include, for example, a step of forming an arbitrary insulating layer. As a specific example, when it is desired to insulate the electroplated layer from other conductor layers, an arbitrary insulating layer may be formed. In addition, as another specific example, when an electroplated layer is formed on the surface of the second hole in the magnetic layer and the entire second hole cannot be filled only by the electroplated layer, an insulating layer filling the second hole may be formed. The insulating layer may be formed by a cured product of a thermosetting resin composition or a photocurable resin composition. As a specific example, a layer of a thermosetting resin composition or a photocurable resin composition may be formed on a magnetic substrate, and the layer may be cured to form an insulating layer.
[0193] The method for manufacturing a magnetic substrate may repeatedly form the magnetic layer and the plating layer, and may repeatedly form an arbitrary conductor layer and an arbitrary insulating layer. Specifically, the magnetic layer and the plating layer may be repeatedly formed, and the magnetic layer and the plating layer may be alternately stacked.
[0194] [Magnetic substrate] The magnetic substrate obtained by the above-mentioned manufacturing method comprises a magnetic layer and an electroplated layer formed on the surface of the magnetic layer. The structure of the magnetic substrate is not particularly limited within the range of comprising a magnetic layer and an electroplated layer. Therefore, the use of the magnetic substrate manufactured by the above-mentioned manufacturing method is not limited. From the viewpoint of utilizing the fact that the electroplated layer can be formed on the surface of the magnetic layer by electroplating, the magnetic substrate preferably comprises a magnetic layer formed with a second hole and an electroplated layer formed in the second hole.
[0195] For example, suppose that a magnetic layer is formed on the main surface of the inner layer substrate, and a conductor layer is formed on the main surface of the magnetic layer. In this case, an electroplated layer can be formed on the main surface of the magnetic layer as the conductor layer by the above method, but for example, a metal foil such as copper foil can also be used to form the conductor layer. Therefore, the conductor layer can also be formed by a method other than the method involved in the above embodiment, omitting electroless plating.
[0196] However, when forming a conductor layer in the second hole formed in the magnetic layer, since the second hole is generally small, it is difficult to form the conductor layer using a metal foil. Therefore, forming a conductor layer in the second hole without using electroless plating cannot be achieved by methods other than the method involved in the above embodiment.
[0197] Therefore, from the viewpoint of providing a new magnetic substrate that cannot be realized by a method other than the manufacturing method involved in the above embodiment and effectively utilizing the above manufacturing method, it is preferred to manufacture a magnetic substrate having a magnetic layer formed with a second hole and a plating layer formed in the second hole by the above manufacturing method. Below, the accompanying drawings are shown to illustrate an example of the magnetic substrate together with its manufacturing method. However, the magnetic substrate and its manufacturing method are not limited to the examples shown below.
[0198] Figures 1 to 12 Schematic cross-sectional views for explaining each step of a method for manufacturing a magnetic substrate according to an example. In the method for manufacturing a magnetic substrate according to this example, Figure 1 As shown, the process includes preparing the inner layer base material 10. In this example, the inner layer base material 10 having a plate shape including a support substrate 11 and base conductor layers 12 formed on both surfaces of the support substrate 11 is shown and described.
[0199] After the inner layer substrate 10 is prepared, Figure 2 As shown, the method for manufacturing a magnetic substrate according to this example includes a step of forming a first hole 10H as a through hole in the inner layer base material 10. The first hole 10H is formed so as to penetrate the inner layer base material 10 in the thickness direction. The diameter of the first hole 10H is not particularly limited, and may be, for example, 200 μm to 800 μm.
[0200] After the first hole 10H is formed, Figure 3 As shown, the method for manufacturing a magnetic substrate according to this example includes a step (step (LF)) of forming a resin composition layer 20 in the first hole 10H of the inner layer substrate 10. Generally, when the resin composition layer 20 is formed in the first hole 10H, the remaining resin composition protrudes or adheres to the outside of the first hole 10H. Therefore, the main surfaces 20U and 20D of the resin composition layer 20 formed in the opening of the first hole 10H are raised and are often uneven.
[0201] After the resin composition layer 20 is formed, Figure 4 As shown, the method for manufacturing the magnetic substrate involved in this example includes a step of grinding the resin composition layer 20 (step (PO)). By grinding, the remaining resin composition protruding or attached outside the first hole 10H is removed, so that the main surfaces 20U and 20D of the resin composition layer 20 can be flat. Usually, the main surface 20U of the resin composition layer 20 after grinding is flush with one main surface 10U of the inner layer substrate 10, and the main surface 20D of the resin composition layer 20 after grinding is flush with the other main surface 10D of the inner layer substrate 10. Unless otherwise specified, multiple surfaces are "flush" means that these surfaces are in the same plane.
[0202] After the resin composition layer 20 is formed, Figure 5 As shown, the method for manufacturing a magnetic substrate according to this example includes a step (step (CU)) of curing the resin composition layer 20 to obtain a magnetic layer 30. Here, an example in which the resin composition layer 20 is cured after being polished is shown, but the magnetic layer 30 may be polished after the resin composition layer 20 is cured to obtain the magnetic layer 30.
[0203] After forming the magnetic layer 30, as Figure 6 As shown, the method for manufacturing a magnetic substrate according to this example includes a step (step (HF)) of forming a second hole 30H as a through hole in the magnetic layer 30. The second hole 30H is formed so as to penetrate the magnetic layer 30 in the thickness direction. The diameter of the second hole 30H can be formed to be smaller than the diameter of the first hole 10H, and there is no limitation on its specific size.
[0204] After the second hole 30H is formed, Figure 7 As shown, the method for manufacturing a magnetic substrate according to this example includes a step (step (EP)) of forming a plating layer 40 on a surface 30S of a magnetic layer 30. The magnetic layer 30 includes: a surface 30S that is not bonded to the inner layer substrate 10, main surfaces 30U and 30D formed at the opening of the first hole 10H, and a hole inner peripheral surface 30I formed in the second hole 30H. The plating layer 40 is usually formed on any one of the main surfaces 30U and 30D of the magnetic layer 30 and the hole inner peripheral surface 30I.
[0205] The entire second hole 30H may be filled with the electroplating layer 40, but a portion of the second hole 30H may not be filled. In the case where a portion of the second hole 30H is not filled with the electroplating layer 40, as shown in FIG. Figure 8 As shown, the method for manufacturing the magnetic substrate according to this example may include a step of forming an insulating layer 50 in the portion of the plating layer 40 that is not filled with the plating layer 40. The insulating layer 50 may be formed by, for example, filling the portion with a curable resin such as a thermosetting resin composition or a photocurable resin composition and curing the resin.
[0206] After the insulating layer 50 is formed, the insulating layer 50 may be polished. When the insulating layer 50 is polished, the electroplating layer 40 may be polished at the same time. Fig. 9 , an example in which the insulating layer 50 and the electroplating layer 40 are polished is shown and described. In this example, by the above-mentioned polishing, the main surface 10U of the inner layer base material 10, the main surface 30U of the magnetic layer 30, the main surface 40U of the electroplating layer 40, and the main surface 50U of the insulating layer 50 are flush. In addition, the main surface 10D of the inner layer base material 10, the main surface 30D of the magnetic layer 30, the main surface 40D of the electroplating layer 40, and the main surface 50D of the insulating layer 50 are flush.
[0207] After the electroplating layer 40 is formed, Fig.10 As shown, the method for manufacturing the magnetic substrate of this example may include a step of forming an arbitrary conductor layer 60 on the inner layer substrate 10, the magnetic layer 30, the electroplated layer 40 and the insulating layer 50. The arbitrary conductor layer 60 may be formed by, for example, electroless plating and electroplating. Fig.11 As shown, a resist layer 70 having a desired pattern is formed on an arbitrary conductor layer 60. Then, the base conductor layer 12, the plating layer 40, and the arbitrary conductor layer 60 that are not covered by the resist layer 70 are removed, and the resist layer 70 is removed.
[0208] Fig.12 is a schematic cross-sectional view of a magnetic substrate involved in one example. Fig.12 In this case, since the conductive layers such as the base conductive layer 12, the plating layer 40, and the arbitrary conductive layer 60 are formed into a spiral shape as a whole, an inductor can be formed using the conductive layers, and thus an inductor-embedded substrate can be obtained as the magnetic substrate 100. In addition, the manufacturing method according to this example can further provide conductive layers other than the base conductive layer 12, the plating layer 40, and the arbitrary conductive layer 60.
[0209] like Fig.12As shown, the magnetic substrate 100 includes: a magnetic layer 30 having a second hole 30H formed therein, and an electroplated layer 40 formed on a surface 30S of the magnetic layer 30. In this example, at least a portion of the electroplated layer 40 is formed in the second hole 30H. The electroplated layer 40 is formed without electroless plating, so the electroplated layer 40 formed in the second hole 30H is in direct contact with the magnetic layer 30. In addition, there is no plating catalyst for electroless plating at the interface between the electroplated layer 40 and the magnetic layer 30 in contact (equivalent to the inner peripheral surface 30I of the hole). It is impossible to form a conductor layer on the surface of the magnetic layer without a plating catalyst in the second hole formed in the magnetic layer in the prior art. Therefore, for the above-mentioned magnetic substrate 100, not only its manufacturing method but also its structure is previously unknown.
[0210] The magnetic substrate can be used, for example, to manufacture an inductor component. The inductor component includes the magnetic substrate. The inductor component usually has an inductor pattern formed by a conductor layer such as a base conductor layer, a plating layer, and an arbitrary conductor layer at least in a portion around the magnetic layer. Such an inductor component can be applied to the component described in Japanese Patent Publication No. 2016-197624. The inductor component includes the inductor built-in substrate.
[0211] The inductor component can be used, for example, as a wiring board for mounting electronic components such as semiconductor chips, or as a (multi-layer) printed wiring board using the wiring board as an inner layer substrate. In addition, for example, it can be used as a chip inductor component obtained by monolithicizing the wiring board, or as a printed wiring board with the chip inductor component mounted on the surface.
[0212] In addition, the wiring board can be used to manufacture various forms of semiconductor devices. The semiconductor device including the wiring board can be suitably used in electrical products (e.g., computers, mobile phones, digital cameras, and televisions) and transportation tools (e.g., motorcycles, cars, trams, ships, and airplanes). Example
[0213] Hereinafter, the present invention will be specifically described by way of examples, but the present invention is not limited to these examples. It should be noted that in the following description, "parts" and "%" indicating amounts refer to "parts by mass" and "mass %" respectively, unless otherwise expressly stated. In addition, unless otherwise stated, the operations shown below are performed at normal temperature and pressure (23° C., 1 atmosphere). Furthermore, the volume content (volume %) is calculated by using mass and specific gravity.
[0214] <Example 1: Production of magnetic varnish 1> 1.92 parts by mass of an epoxy resin (“ZX-1059” manufactured by Nippon Steel Chemical Materials Co., Ltd., a mixture of bisphenol A epoxy resin and bisphenol F epoxy resin, epoxy equivalent 169 g / eq.), 2.18 parts by mass of a phenolic resin containing a triazine skeleton (“LA-7054” manufactured by DIC Corporation, a 60% solid content MEK solution with a hydroxyl equivalent of about 125 g / eq.), 1.67 parts by mass of a phenoxy resin (“YL7553BH30” manufactured by Mitsubishi Chemical Corporation, a 1:1 solution of MEK and cyclohexanone with a solid content of 30%), 0.43 parts by mass of a dispersant (“PB-821” manufactured by Ajinomoto Fine Techno Co., Ltd., a cationic dispersant), 3 parts by mass of a solvent (cyclohexanone), and ferrite powder (“M03S” manufactured by Powdertech Co., Ltd., Fe—Mn ferrite, average particle size 0.5 μm, specific gravity 5.1 μm) were mixed with the mixture. 2 / g) 22.09 parts by mass, and alloy powder ("AKT-PB (5)" manufactured by Mitsubishi Steel, Ltd., Fe-Ni alloy, average particle size 5.0 μm, specific gravity 8.0 m 2 / g) were mixed to prepare magnetic varnish 1.
[0215] <Example 2: Production of magnetic varnish 2> Ferrite powder ("M03S" manufactured by Powdertech, Fe-Mn ferrite, average particle size 0.5 μm, specific gravity 5.1 μm) was prepared. 2 / g) was changed from 22.09 parts by mass to 30.00 parts by mass. In addition, alloy powder ("AKT-PB (5)" manufactured by Mitsubishi Steel, Ltd., Fe-Ni alloy, average particle size 5.0 μm, specific gravity 8.0 m 2 / g) was changed from 73.74 parts by mass to 30.00 parts by mass. Magnetic varnish 2 was produced in the same manner as in Example 1 except for the above matters.
[0216] <Example 3: Production of magnetic varnish 3> Ferrite powder ("M03S" manufactured by Powdertech, Fe-Mn ferrite, average particle size 0.5 μm, specific gravity 5.1 μm) was prepared. 2 / g) was changed from 22.09 parts by mass to 50.00 parts by mass. In addition, alloy powder ("AKT-PB (5)" manufactured by Mitsubishi Steel, Ltd., Fe-Ni alloy, average particle size 5.0 μm, specific gravity 8.0 m 2 / g) was changed from 73.74 parts by mass to 22.00 parts by mass. Magnetic varnish 3 was produced in the same manner as in Example 1 except for the above matters.
[0217] <Example 4: Production of Magnetic Varnish 4> In addition to the ferrite powder (M03S manufactured by Powdertech, Fe-Mn ferrite, average particle size 0.5 μm, specific gravity 5.1 μm 2 / g) 22.09 parts by mass were converted into alloy powder (fine powder alloy "CVD iron powder" manufactured by JFE Mining Co., Ltd., Fe-Cr-Si alloy, average particle size 0.7 μm, specific gravity 6.9 μm 2 Magnetic varnish 4 was produced in the same manner as in Example 1 except that the amount of MgSO4 / g was 30.92 parts by mass.
[0218] <Example 5: Production of Magnetic Varnish 5> In addition to the ferrite powder (M03S manufactured by Powdertech, Fe-Mn ferrite, average particle size 0.5 μm, specific gravity 5.1 μm 2 / g) 22.09 parts by mass were converted into ferrite powder ("MZ03S" manufactured by Powdertech, Fe-Mn-Zn ferrite, average particle size 0.5 μm, specific gravity 5.1 μm 2 Magnetic varnish 5 was produced in the same manner as in Example 1 except that the amount of MgSO4 / MgSO4 was 22.09 parts by mass.
[0219] <Example 6: Production of Magnetic Varnish 6> In addition to alloy powder (Mitsubishi Steel Corporation "AKT-PB (5)", Fe-Ni alloy, average particle size 5.0μm, specific gravity 8.0m 2 / g) 73.74 parts by mass were converted into alloy powder ("AKT-PB-3Si(5)" manufactured by Mitsubishi Steel, Ltd., Fe-Ni-Si alloy, average particle size 5.0 μm, specific gravity 8.0 μm 2 Magnetic varnish 6 was produced in the same manner as in Example 1 except that the amount of MgSO4 / MgSO4 was 73.74 parts by mass.
[0220] <Example 7: Production of Magnetic Varnish 7> In addition to alloy powder (Mitsubishi Steel Corporation "AKT-PB (5)", Fe-Ni alloy, average particle size 5.0μm, specific gravity 8.0m 2 / g) 73.74 parts by mass were converted into alloy powder ("AW2-08 PF3F" manufactured by Epson Atmix, Fe-Si-Cr alloy, average particle size 3.0 μm, specific gravity 6.9 μm 2 Magnetic varnish 7 was produced in the same manner as in Example 1 except that MgSO4 / MgSO4 / g) was 50.00 parts by mass.
[0221] <Example 8: Production of Magnetic Paste 8> 1.70 parts by mass of epoxy resin (ZX-1059 manufactured by Nippon Steel Chemicals, a mixture of bisphenol A epoxy resin and bisphenol F epoxy resin, epoxy equivalent 169 g / eq.), 1.42 parts by mass of epoxy resin (630 manufactured by Mitsubishi Chemical Corporation, a glycidylamine epoxy resin, epoxy equivalent 95 g / eq.), 1.60 parts by mass of epoxy resin (ZX-1658GS manufactured by Nippon Steel Chemicals, a cyclic aliphatic diglycidyl ether, cyclic 135 g / eq.), 4.90 parts by mass of an oxygen equivalent, 0.57 parts by mass of a dispersant (“PB-821” manufactured by Ajinomoto Fine Technologies, a cationic dispersant), 0.47 parts by mass of a curing accelerator (“2MZA-PW” manufactured by Shikoku Chemicals, an imidazole epoxy resin curing accelerator), and 0.57 parts by mass of a ferrite powder (“M03S” manufactured by Powdertech, a Fe-Mn ferrite with an average particle size of 0.5 μm and a specific gravity of 5.1 μm). 2 / g) 17.75 parts by mass, and alloy powder ("AKT-PB (5)" manufactured by Mitsubishi Steel, Ltd., Fe-Ni alloy, average particle size 5.0 μm, specific gravity 8.0 m 2 / g) and 59.09 parts by mass were mixed to produce a magnetic paste 8.
[0222] <Example 9: Production of Magnetic Ink 9> 4.6 parts by mass of epoxy resin ("ZX-1059" manufactured by Nippon Steel Chemicals, a mixture of bisphenol A epoxy resin and bisphenol F epoxy resin, epoxy equivalent 169 g / eq.), 1.42 parts by mass of epoxy resin ("630" manufactured by Mitsubishi Chemical, a glycidylamine epoxy resin, epoxy equivalent 95 g / eq.), and 1.6 parts by mass of epoxy resin ("ZX-1658GS" manufactured by Nippon Steel Chemicals, a cyclic aliphatic diglycidyl ether, epoxy equivalent 169 g / eq.). 135 g / eq.), 2.0 parts by mass of dispersant (“PB-821” manufactured by Ajinomoto Fine Technologies Co., Ltd., cationic dispersant), 0.57 parts by mass of curing accelerator (“2MZA-PW” manufactured by Shikoku Chemical Co., Ltd., imidazole epoxy resin curing accelerator), 0.47 parts by mass of solvent (butyl carbitol acetate), 1.0 parts by mass of ferrite powder (“M03S”, Fe-Mn ferrite, average particle size 0.5 μm, specific gravity 5.1 μm 2 / g, Powdertech Co., Ltd.) 17.75 parts by mass, and alloy powder (Mitsubishi Steel Corporation "AKT-PB (5)", Fe-Ni alloy, average particle size 5.0 μm, specific gravity 8.0 m 2 / g) and 59.09 parts by mass were mixed to prepare magnetic ink 9.
[0223] <Comparative Example 1: Production of Magnetic Varnish 10> Ferrite powder ("M03S" manufactured by Powdertech, Fe-Mn ferrite, average particle size 0.5 μm, specific gravity 5.1 μm) was prepared. 2 / g) was changed from 22.09 parts by mass to 50.00 parts by mass. In addition, alloy powder ("AKT-PB (5)" manufactured by Mitsubishi Steel, Ltd., Fe-Ni alloy, average particle size 5.0 μm, specific gravity 8.0 m 2 / g) was changed from 73.74 parts by mass to 8.00 parts by mass. Furthermore, 3 parts by mass of the solvent (cyclohexanone) was not used. Except for the above matters, the magnetic varnish 10 was produced in the same manner as in Example 1.
[0224] <Manufacturing of resin sheet> As a support, a PET film ("Lumirror R80" manufactured by Toray Industries, Ltd., thickness 38 μm, softening point 130°C, hereinafter sometimes referred to as "release PET") which had been subjected to release treatment with an alkyd resin-based release agent ("AL-5" manufactured by Lintec) was prepared. The resin varnishes 1 to 7 and 10 manufactured in Examples 1 to 7 and Comparative Example 1 were coated on the support using a die coater so that the thickness of the resin composition layer after drying would be 100 μm, and dried at 65°C to 115°C (average 100°C) for 7 minutes to obtain a resin sheet.
[0225] <Plating Test 1: Formation of Conductor Layer by Plating Using Resin Sheet> As the inner layer substrate, a glass cloth-based epoxy resin double-sided copper-clad laminate (copper foil thickness 18 μm, substrate thickness 0.3 mm, "R5715ES" manufactured by Panasonic) was prepared by etching both sides by 1 μm with a microetchant ("CZ8100" manufactured by MEC) to roughen the copper surface.
[0226] A 200 mm square slice was cut from each resin sheet manufactured in Examples 1 to 7 and Comparative Example 1. The cut slices (200 mm square) were laminated on both sides of the inner layer substrate using a batch vacuum pressure laminator (a two-stage stacking laminator "CVP700" manufactured by Nikko-Materials) in such a way that the resin composition layer was in contact with the center of the inner layer substrate. Lamination was performed by reducing the pressure for 30 seconds to make the air pressure below 13 hPa, and then pressing at 100°C and a pressure of 0.74 MPa for 30 seconds. Then, the resin composition layer was thermally cured by heating at 130°C for 30 minutes and then at 180°C for 30 minutes to form a magnetic layer. The surface of the formed magnetic layer was polished.
[0227] The surface of the polished magnetic layer was electroplated with copper sulfate as electroplating. The magnetic layer was used as a cathode, the copper plate was used as an anode, and a current density of 2.0 A / dm was set in a copper sulfate solution as a plating solution. 2 The plating solution was composed of the following: Wako Pure Chemical Industries, Ltd. "Copper sulfate pentahydrate" 79g / L Wako Pure Chemical Industries, Ltd. "Sulfuric acid" 154mL / L Wako Pure Chemical Industries, Ltd. "Sodium Chloride" 65mg / L Atotech Japan Co., Ltd. "Additive Cupracid HL", surfactant 30mL / L Atotech Japan Co., Ltd. "Correction Cupracid GS", organic sulfur compounds, 0.1mL / L
[0228] After the electroplating, an annealing treatment was performed at 180° C. for 60 minutes to obtain an evaluation substrate. The evaluation substrate was observed to determine whether a conductor layer (electroplating layer) was formed on the surface of the magnetic layer. The case where the electroplating layer could be formed on the entire surface of the magnetic layer was evaluated as "good", and the case where the electroplating layer could not be formed was evaluated as "bad".
[0229] <Plating Test 2: Formation of Conductive Layer by Plating Using Magnetic Paste or Magnetic Ink> As the inner layer substrate, a glass cloth-based epoxy resin double-sided copper-clad laminate (copper foil thickness 18 μm, substrate thickness 0.3 mm, "R5715ES" manufactured by Panasonic) was prepared by etching both sides by 1 μm with a microetchant ("CZ8100" manufactured by MEC) to roughen the copper surface.
[0230] The magnetic paste prepared in Example 8 and the magnetic ink prepared in Example 9 were uniformly applied to the inner layer substrate using a scraper so that the thickness of the magnetic layer after curing was 100 μm to form a resin composition layer. The resin composition layer was thermally cured by heating at 130° C. for 30 minutes and further at 150° C. for 30 minutes to form a magnetic layer. After the surface of the formed magnetic layer was polished, a heat treatment was performed at 180° C. for 30 minutes to further promote curing.
[0231] On the surface of the magnetic layer that has been subjected to the grinding treatment, copper sulfate electrolytic plating is performed as electroplating. The electroplating is performed in the same manner as the electroplating in the above-mentioned electroplating test 1. After the electroplating, an annealing treatment is performed at 180° C. for 60 minutes to obtain an evaluation substrate. The evaluation substrate is observed to determine whether a conductor layer (electroplating layer) is formed on the surface of the magnetic layer. The case where the electroplating layer can be formed on the entire surface of the magnetic layer is evaluated as "good", and the case where the electroplating layer cannot be formed is evaluated as "bad".
[0232] <Magnetic Property Test 1: Measurement of Relative Magnetic Permeability and Loss Factor of Magnetic Layer Obtained from Resin Sheet> A 200 mm square sheet was cut from each resin sheet manufactured in Examples 1 to 7 and Comparative Example 1. A batch vacuum pressure laminator (a two-stage stacking laminator "CVP700" manufactured by Nikko-materials) was used to laminate the cut sheet (200 mm square) on one side of a polyimide film ("Upilex 25S" manufactured by Ube Industries, Ltd., 25 μm thick, 240 mm square). The above lamination is performed in such a way that the resin composition layer of the sheet is in contact with the center of the smooth surface of the polyimide film. In addition, the above lamination is performed by reducing the pressure for 30 seconds to make the air pressure below 13 hPa, and then pressing at 100°C and a pressure of 0.74 MPa for 30 seconds. By lamination, a multilayer film having a layer structure of a support body / resin composition layer / polyimide film is obtained.
[0233] After peeling off the support, heat at 190°C for 90 minutes to thermally cure the resin composition layer. Then, peel off the polyimide film to obtain a sheet-like cured product. This cured product is equivalent to the magnetic layer obtained from the resin sheet. The obtained sheet-like cured product is cut to obtain a ring-shaped evaluation sample with an outer diameter of 19.2 mm and an inner diameter of 8.2 mm. Using the magnetic material test fixture "16454A" manufactured by Keysight and the impedance analyzer "E4991B" manufactured by Keysight, the relative magnetic permeability (μ') and loss factor (tanδ) of the evaluation sample were measured at a measurement frequency of 20 MHz and room temperature of 23°C. The loss factor tanδ is calculated by the following formula "tanδ=μ" / μ'".
[0234] <Magnetic Property Test 2: Determination of Relative Magnetic Permeability and Loss Factor of Magnetic Layer Obtained from Magnetic Paste or Magnetic Ink> As a support, a polyethylene terephthalate (PET) film ("PET501010" manufactured by Lintec Corporation, thickness 50 μm) treated with a silicone release agent was prepared. The magnetic paste prepared in Example 8 and the magnetic ink prepared in Example 9 were uniformly applied to the release surface of the PET film using a scraper so that the thickness of the magnetic layer after curing became 100 μm, thereby obtaining a resin sheet having a support and a resin composition layer.
[0235] The obtained resin sheet is heated at 190°C for 90 minutes to thermally cure the resin composition layer. Then, the support is peeled off to obtain a sheet-like cured product. The cured product is equivalent to a magnetic layer obtained from a magnetic paste or a magnetic ink. The obtained sheet-like cured product is cut to obtain a ring-shaped evaluation sample with an outer diameter of 19.2 mm and an inner diameter of 8.2 mm. Using the magnetic material test fixture "16454A" manufactured by Keysight and the impedance analyzer "E4991B" manufactured by Keysight, the relative magnetic permeability (μ') and loss factor (tanδ) of the evaluation sample are measured at a measurement frequency of 20 MHz and a room temperature of 23°C. The loss factor tanδ is calculated by the following formula "tanδ=μ" / μ'".
[0236] <Resistance measurement test: Measurement of volume resistance of magnetic layer> A sheet-like solidified product was obtained by the same method as in Magnetic Property Tests 1 and 2. The obtained sheet-like solidified product was cut to obtain a 10 cm square evaluation sample. The volume resistivity of the sample was measured using an insulation resistance meter "R8340" manufactured by Advantest.
[0237] <Surface roughness measurement test: Measurement of surface roughness of electroplated layer> The arithmetic mean roughness Ra of the electroplated layers formed in the electroplating test 1 and the electroplating test 2 was determined by using a non-contact surface roughness meter (WYKO NT3300 manufactured by Veeco Instruments) using a VSI mode and a 50x lens with the measurement range set to 121 μm × 92 μm to obtain the Ra value. The Ra value was determined by finding the average value of 10 randomly selected points.
[0238] <Results> The results of the above-mentioned Examples and Comparative Examples are shown in the following table. In the following table, the abbreviations have the following meanings. CH: Cyclohexanone. BCA: Butyl Carbitol Acetate. Amount of magnetic powder (wt%): The amount of (A) magnetic powder relative to 100% by mass of the nonvolatile components of the resin composition. Amount of magnetic powder (vol%): The amount of (A) magnetic powder relative to 100% by volume of the nonvolatile components of the resin composition. Amount of alloy powder (wt%): Amount of alloy powder (A-1) relative to 100% by mass of the nonvolatile components of the resin composition. Amount of alloy powder (vol%): Amount of alloy powder (A-1) relative to 100% by volume of the nonvolatile components of the resin composition. Alloy powder / magnetic powder (wt%): the amount of the alloy powder (A-1) relative to 100% by mass of the magnetic powder (A). Alloy powder / magnetic powder (vol%): the amount of the alloy powder (A-1) relative to 100 volume % of the magnetic powder (A). Plating formation: Whether the plating layer can be formed by electroplating. Relative magnetic permeability: corresponds to the relative magnetic permeability of a cured product of the resin composition of the magnetic layer. Loss factor: corresponds to the loss factor of the cured product of the resin composition of the magnetic layer. Volume Resistivity: Volume resistance of the magnetic layer. Surface roughness: The surface roughness of the electroplating layer.
[0239] [Table 1] [Table 1. Results of Examples 1 to 5]
[0240] [Table 2] [Table 2. Results of Examples 6 to 9 and Comparative Example 1]
[0241] Explanation of symbols 10 Inner substrate 10H First hole 10U, 10D Main surface of inner substrate 11 Support base plate 12 Base material conductor layer 20 Resin composition layer 20U, 20D Main surface of resin composition layer 30 Magnetic layer 30H Second hole 30S Surface of magnetic layer 30U, 30D Main surface of magnetic layer 30I Inner surface of the hole of the magnetic layer 40 Electroplating layer 50 Insulation layer 60 Any conductor layer 70 Anti-corrosion layer 100 Magnetic substrate.
Claims
1. A method for producing a magnetic substrate, comprising: producing a magnetic substrate comprising a magnetic layer and a conductor layer formed on a surface of the magnetic layer; The manufacturing method includes a step (EP) of forming a conductor layer on the surface of the magnetic layer by electroplating. The magnetic layer comprises a cured product of a resin composition, wherein the resin composition comprises (A) a magnetic powder and (B) a thermosetting resin. The (A) magnetic powder contains 30% by mass or more of the (A-1) alloy powder relative to 100% by mass of the (A) magnetic powder.
2. The method for manufacturing a magnetic substrate according to claim 1, wherein: Before the process (EP), including: a step of forming a resin composition layer (LF) comprising a resin composition, and A step (CU) of curing the resin composition layer to form a magnetic layer.
3. The method for manufacturing a magnetic substrate according to claim 2, wherein: There is no step of forming a conductor layer on the surface of the magnetic layer by a method other than electroplating between the step (CU) and the step (EP).
4. The method for manufacturing a magnetic substrate according to claim 2, wherein: Step (LF) includes forming a resin composition layer in the first holes of the substrate in which the first holes are formed.
5. The method for manufacturing a magnetic substrate according to claim 1, wherein: Prior to step (EP), a step (HF) of forming a second hole in the magnetic layer is included. Step (EP) includes the step of forming a conductor layer on the surface of the magnetic layer in the second hole by electroplating.
6. The method for manufacturing a magnetic substrate according to claim 1, wherein: The amount of the (A) magnetic powder is 60% by mass or more relative to 100% by mass of the nonvolatile components in the resin composition.
7. The method for manufacturing a magnetic substrate according to claim 1, wherein: The relative magnetic permeability of the cured product at a measurement frequency of 20 MHz was 10 or more.
8. The method for manufacturing a magnetic substrate according to claim 1, wherein: (A-1) The alloy powder includes one or more selected from the group consisting of Fe—Ni alloy powder, Fe—Cr—Si alloy powder, and Fe—Ni—Cr alloy powder.
9. A magnetic substrate comprising a magnetic layer having a hole formed therein and a conductor layer formed in the hole, in, The magnetic layer is in direct contact with the conductive layer, and no plating catalyst exists at the interface between the magnetic layer and the conductive layer. The magnetic layer comprises a cured product of a resin composition, wherein the resin composition comprises (A) a magnetic powder and (B) a thermosetting resin. The (A) magnetic powder contains 30% by mass or more of the (A-1) alloy powder relative to 100% by mass of the (A) magnetic powder.
10. The magnetic substrate according to claim 9, wherein The conductor layer is formed of copper.
Citation Information
Patent Citations
Silicone-containing polyimide resin, silicone-containing polyamic acid and their production
JP2000319386A
Polyimidesilicone resin, solution composition thereof, and polyimidesilicone resin coating film
JP2002012667A
Thermosetting resin composition containing modified polyimide resin
JP2006037083A
Inductor component, manufacturing method for inductor component, printed wiring board incorporating inductor component
JP2016197624A